Method for producing a porous anode for a lithium-ion secondary battery, the resulting anode, and a battery comprising said anode

JP2024503284A5Pending Publication Date: 2024-12-19I TEN
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023539920
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2020-12-29
Filing Date
2021-12-23
Publication Date
2024-12-19

AI Technical Summary

Technical Problem

Existing lithium-ion batteries face challenges such as safety risks from organic solvent-based electrolytes, local state of charge imbalances leading to instability, and high manufacturing costs due to the use of organic binders and solvents like NMP, which complicates the drying process and affects electrode performance.

Method used

A method for producing a porous anode with a porosity of 25-50% and nanoparticle agglomerates of niobium and titanium oxides, using a colloidal suspension deposited on a substrate, followed by drying and consolidation, and optionally coating with an electronically conductive material to enhance conductivity and stability.

Benefits of technology

The method results in a high-capacity anode with rapid recharge capability, reduced risk of lithium plating, and improved safety, while minimizing manufacturing costs and maintaining high energy density across a wide temperature range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000041_0000
    Figure 00000041_0000
Patent Text Reader

Abstract

1. A method for producing an anode having a porosity between 25% and 50% by volume, comprising: (a) a substrate and a porous layer having an average primary diameter D 50 and a colloidal suspension or paste composed of monodisperse primary nanoparticles in agglomerate form or dispersed therein of at least one active material of anode A selected from niobium oxide having a structure of niobium oxide with titanium, germanium, cerium, lanthanum, copper or tungsten, (b) a layer of said colloidal suspension or paste provided in step (a) is deposited on at least one side of said substrate by a method selected from the group comprising electrophoresis, a printing process, preferably inkjet printing or flexographic printing, a coating method, preferably doctor blade coating, roll coating, curtain coating, dip coating or slot die passing, (c) said layer obtained in step (b) is dried and consolidated by pressing and / or heating in order to obtain a porous layer.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of electrochemistry, and more particularly to electrochemical systems. It more particularly relates to electrodes used in batteries with a capacity of more than 1 mAh. The present invention relates to a new method for producing porous anodes that can be used in electrochemical systems such as high-power batteries, particularly lithium-ion batteries. The method uses nanoparticles of anode material.

[0002] The invention also relates to a mesoporous anode obtained by this method. The invention also relates to a battery comprising such a porous anode. In this respect, the invention also relates to a method for preparing a lithium-ion battery formed from such a mesoporous anode, the mesoporous anode being in contact with a porous separator, which is also in contact with a porous cathode. These porous electrode / separator assemblies can be impregnated with a liquid electrolyte.

[0003] More precisely, the invention relates to an anode that combines the following features: high volumetric capacity (mAh / cm 3 ), a sufficiently high insertion potential to allow rapid recharging without any risk of lithium plating, and no significant volume fluctuations during the charging and discharging steps of the battery, so that said battery can be used in the form of rigid monoblock fully solid and mesoporous structures. [Background technology]

[0004] An ideal battery for powering autonomous electric devices (phones and laptops, handheld tools, autonomous sensors, etc.) or for powering electric vehicles should have a long life, be able to store large amounts of both energy and power, be able to function over a very wide temperature range, and not be at risk of overheating or exploding.

[0005] Currently, these electrical devices are essentially powered by lithium-ion batteries, which have the highest energy density among the various storage technologies proposed. There are various structures and chemical compositions of the electrodes that allow the creation of lithium-ion batteries. Methods for producing lithium-ion batteries are presented in numerous patents, and the works ''Advances in Lithium-Ion Batteries'' (Ed. W. van Schalkwijk and B. Scrosati) published in 2002 (Kluever Academic / Plenum Publishers) and ''Lithium Batteries. Science and Technology'' by C. Julien, A. Mauger, A. Vijh, and K. Zaghib (Springer, Heidelberg 2016) provide a good overview.

[0006] Lithium ion battery electrodes can be manufactured using known coating techniques, such as roll coating, curtain coating, slot die coating, doctor blade coating, and tape casting, among others.

[0007] In these methods, the active material used to make the electrodes is used in the form of a powder suspension with an average particle size between 5 μm and 15 μm in diameter. These particles are integrated into an ink consisting of these particles, an organic binder, and a powdered filler of electronically conductive material (conductive filler), typically carbon black. This ink is deposited on the surface of a metal substrate and then dried to remove the organic solvents it contains, leaving only a porous deposit on the surface of the metal strip consisting of particles of active material mechanically bound together by the organic binder and electrically connected by the carbon black.

[0008] These techniques make it possible to obtain layers with a thickness between about 20 μm and about 400 μm. Depending on the thickness of the layers, their porosity and the size of the active particles, the power and energy of the battery can be adjusted.

[0009] According to the prior art, the ink (or paste) deposited to form the electrode contains particles of active material, but also (organic) binders, carbon powder to ensure electrical contact between the particles and the solvent that is evaporated in a drying step of the electrode. To improve the quality of the electrical contact between the particles and to compact the deposited layer, a calendering step is carried out on the electrode. After this compaction step, the active particles of the electrode occupy about 60-70% of the volume of the deposit, which means that typically 30-40% of the porosity remains between the particles.

[0010] To optimize the volumetric energy density of lithium-ion batteries produced by these conventional manufacturing methods, it would be very useful to reduce the porosity of the electrodes. Reducing the porosity, or in other words increasing the amount of active material per unit volume of the electrode, can be achieved in several ways.

[0011] At one extreme, the electrode films with the highest energy density per volume are made using vacuum deposition techniques, such as PVD. These films are completely dense and not porous. However, because these completely solid films do not contain liquid electrolytes to facilitate ion transport or electronically conductive inclusions to facilitate the transport of charge, their thickness is limited to a few microns to prevent their resistance from becoming too large.

[0012] With standard inking techniques, it is also possible to increase the volumetric energy density by optimizing the size distribution of the deposited particles. In fact, it is possible to achieve a density of about 70% by optimizing the particle size distribution, as shown, for example, in the review paper ''Effect of particle size distribution on sintering of agglomerate-free submicron alumina powder compacts'' by J. Ma and L.C. Lim, published in 2002 in J.European Ceramic Society 22 (2002), pp. 2197-2208. An electrode with 30% porosity containing conductive charges and impregnated with a lithium-ion conductive electrolyte will have a volumetric energy density about 35% higher than the same electrode with 50% porosity made of particles of monodisperse size.

[0013] Furthermore, based on the impregnation with highly ionically conductive phases and the addition of electronic conductors, the thickness of these electrodes can be significantly increased compared to what can be achieved with vacuum deposition techniques. These increases in thickness also contribute to an increase in the energy density of the battery cell.

[0014] Although this increases the energy density of the electrode, this size distribution of active material particles is not without problems. Different sized particles in the electrode will have different capacities and will be locally charged and / or discharged more or less depending on their size under the influence of the same charge and / or discharge current. When the battery is no longer under current load, the local charge states between the particles will be balanced again, but during these transient phases, local imbalances may result in particles locally loaded outside their stable voltage range. These imbalances in the local charge states will be more pronounced at higher current densities. These imbalances therefore result in loss of cycling performance, safety risks, and limited power output of the battery cell.

[0015] These effects of the particle size distribution of the active material on the current / voltage relationship of the electrode were investigated and simulated by ST Taleghani et al. in the publication ''A study on the effect of porosity and particles size distribution on Li-ion battery performance'' published in J. Electrochemical Society, 164(11) 2017, p. E3179-E3189.

[0016] In prior art electrode inking techniques, the particles of active material generally have a size between 5 μm and 15 μm. The contact between two adjacent particles is essentially punctate, and the particles are bound by an organic binder, most often PVDF.

[0017] The liquid electrolytes used to impregnate the electrodes consist of aprotic solvents with lithium salts dissolved in them. These organic electrolytes are highly flammable and can cause violent combustion of the battery cell, especially when the cathode active materials are loaded at voltage ranges outside their stable voltage range or when hot spots occur locally within the cell.

[0018] To address these safety concerns inherent in conventional Li-ion battery cell construction, it is necessary: · Replacing organic solvent-based electrolytes with highly temperature stable ionic liquids. However, ionic liquids do not wet the surfaces of organic materials, and the presence of PVDF and other organic binders in conventional battery electrodes prevents wetting of the electrodes by this type of electrolyte, affecting the performance of the electrodes. Ceramic separators have been developed to solve this problem at the electrolyte junction between the electrodes, but the presence of organic binders in the electrodes continues to pose a problem for the use of ionic liquid electrolytes.

[0019] Uniform particle size to avoid local imbalances in the state of charge that can result during hard discharge in locally stressed active materials outside the traditional voltage operating range of the active material. This optimization can then adversely affect the energy density of the cell.

[0020] Uniform distribution of the conductive filler (carbon black) in the electrodes to avoid areas of localized higher electrical resistance that could lead to the formation of hot spots during power delivery operation of the battery.

[0021] More specifically, regarding the methods for manufacturing battery electrodes according to the prior art, their manufacturing cost depends in part on the nature of the solvent used: in addition to the intrinsic cost of the active material, the cost of manufacturing an electrode is essentially based on the complexity of the ink used (binder, solvent, carbon black...).

[0022] The main solvent used to make electrodes for lithium-ion batteries is NMP. NMP is an excellent solvent for dissolving PVDF, which acts as a binder in the ink formulation. Drying the NMP contained in the electrodes is a real economic problem. The high boiling point of NMP, combined with the very low vapor pressure, makes drying difficult. The solvent vapor needs to be recovered and reprocessed. Furthermore, to ensure better adhesion of the electrodes to the substrate, the drying temperature of NMP should not be too high, which tends to further increase the drying time and costs, as described in the publication ''Technical and economic analysis of solvent-based lithium-ion electrode drying with water and NMP'' by DL Wood et al., published in Drying Technology, vol. 36, n° 2 (2018).

[0023] Other cheap solvents, especially water and ethanol, can be used to make the ink. However, their surface tension is greater than that of NMP, and they do not wet the surface of the metal current collector as effectively. Furthermore, particles, especially carbon black nanoparticles, have a tendency to agglomerate in water. These agglomerations result in a non-uniform distribution of the components (binder, carbon black...) that go into the composition of the electrode. Moreover, whether in water or in ethanol, traces of water can remain adsorbed on the surface of the active material particles even after drying.

[0024] Finally, in addition to the problem of formulating inks to achieve high performance and low cost electrodes, it is also important to note that the ratio between the energy density and the power density of the electrodes can be adjusted depending on the particle size of the active material and, indirectly, on the porosity of the electrode deposits and their thickness. The review paper ''Optimization of Porosity and Thickness of a Battery Electrode by Means of a Reaction-zone Model'' by J. Newman, published in J. Electrochem. Soc., Vol. 142, n° 1 (1995), shows the respective effects of the thickness of the electrodes and their porosity on their discharge power and energy density.

[0025] In addition to the structure and manufacturing method of the battery cell, the choice of electrode material is also fundamental. The energy stored in a battery is the product of the electrode capacity in Ah or mAh multiplied by the operating voltage of the cell, which is the difference between the lithium insertion potentials at the anode and cathode.

[0026] The lower the lithium insertion potential of the anode, the higher the energy of the battery at equal capacity. However, anodes with low insertion potentials, such as graphite, run the risk of lithium "plating" at high recharge currents. Indeed, to rapidly recharge a battery, large amounts of lithium must be rapidly inserted into the anode. A high lithium concentration on the surface of the anode, in conjunction with a very low potential, would favor the precipitation of metallic lithium dendrites, thereby inducing a short circuit in the cell.

[0027] Furthermore, if one wishes to obtain a battery with a very rapid rechargeability, without the safety risks due to lithium plating, and because of this rechargeability the energy density of the cells remains high, it is simultaneously necessary: - Using anodes that insert lithium at relatively high voltages (higher than 0.5 V / Li) to avoid the formation of lithium dendrites during the fast recharge phase. These anodes also need to have a very high mass capacity in order to compensate for the energy loss by reducing the operating voltage by increasing their capacity. - To have electrodes with a very large specific surface area and as uniform a particle size (thickness of the insertion zone) as possible, in order to avoid dynamic imbalance. - Having electrodes with excellent ionic and electronic conductivity. - Having an electrolyte with very good ionic conductivity with high transport number and low polarization resistance. Summary of the Invention [Problem to be solved by the invention]

[0028] The present invention aims to propose a lithium-ion battery that has at least some of these technical characteristics, and preferably all of them. According to the invention, this problem is solved by a judicious choice of the material of the anode and its structure, and by a manufacturing method that makes it possible to obtain an anode with such a structure. [Means for solving the problem]

[0029] According to the invention, this problem is solved by a method for manufacturing a porous anode for a battery designed to have a capacity of more than 1 mAh, comprising an anode, a separator and a cathode, said anode having a porosity of between 25 and 50% by volume, preferably about 35% by volume, the pores having an average diameter of less than 50 nm, according to a particular method forming a first subject of the invention. The anode according to the invention is advantageously used in a battery designed to have a capacity of more than 1 mAh.

[0030] The method for manufacturing a porous anode for a battery according to the present invention comprises the following steps: (a) a substrate and a mean primary diameter D 50 and a colloidal suspension or paste composed of agglomerated form or dispersed monodisperse primary nanoparticles of at least one active material of anode A having the formula: NbO 5-δ , Nb 18 W 16 O 93-δ , Nb 16 W5O 55-δ , where 0 ≤ x < 1 and 0 ≤ δ ≤ 2; ·TiNbO 7-δ , Ti 1-x M 1 x Nb 2-y M 2 y O 7-δ , Li w Ti 1-x M 1 x Nb 2-y M 2 y O7-δ , where M 1 and M. 2 are at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn, and M 1 and M. 2 may be the same or different from each other, and 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and 0≦δ≦0.3; ·Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , in the formula, M 1 and M. 2 are each at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; M 1 and M. 2 may be the same or different from each other, M 3 is at least one halogen; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; ·TiNbO 7-z M 3 z , Li w TiNbO 7-z M 3 z , where M 3is at least one halogen, preferably at least one halogen selected from F, Cl, Br, I, or mixtures thereof, and 0≦w≦5 and 0 <z≦0.3である; ·Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x Ce x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Ce x Nb 2-y M1 y O 7-z M 2 z , in the formula, M 1 and M. 2 are each at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; M 1 and M. 2 may be the same or different from each other, 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; ·Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Ti 1-x Ce x Nb 2-y M 1 y O 7-z , Li w Ti 1-x Ce x Nb 2-y M 1 y O 7-z , in the formula, M 1 is at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z<1, preferably 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z<0.3; selected from the group formed by (b) depositing a layer from said colloidal suspension or paste provided in step (a) on at least one side of said substrate by a method selected from the group consisting of electrophoresis, extrusion, a printing method, preferably inkjet printing or flexographic printing, a coating method, preferably formed by doctor blade coating, roll coating, curtain coating, dip coating or slot die passing, (c) drying the layer obtained in step (b) and consolidating it by pressing and / or heating to obtain a porous layer.

[0031] Advantageously, said active material of anode A may also be selected from oxides of niobium and mixed oxides of niobium with titanium, germanium, cerium, lanthanum, copper or tungsten, preferably NbO 5-δ , Nb 18 W 16 O 93-δ , Nb 16 W5O 55-δ , where 0 ≤ x < 1 and 0 ≤ δ ≤ 2; ·TiNbO 7-δ , where 0<δ≦0.3, Ti 1-x M 1 x Nb 2-y M 2 y O 7-δ , Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7-δ , where M 1 and M. 2 are at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn, and M 1 and M. 2may be the same or different from each other, and 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and 0≦δ≦0.3; ·Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , in the formula, M 1 and M. 2 are each at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; M 1 and M. 2 may be the same or different from each other, M 3 is at least one halogen; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; ·TiNbO 7-z M 3 z , Li w TiNbO 7-z M 3 z , where M 3 is at least one halogen, preferably at least one halogen selected from F, Cl, Br, I, or mixtures thereof, and 0≦w≦5 and 0 <z≦0.3である; ·Ti 1-x Ge x Nb 2-y M 1 y O 7-z M2 z ,There w You 1-x Ge x Nb 2-y M 1 y THE 7-z M 2 z ,You 1-x The x Nb 2-y M 1 y THE 7-z M 2 z ,There w You 1-x The x Nb 2-y M 1 y THE 7-z M 2 z ,You 1-x Cu x Nb 2-y M 1 y THE 7-z M 2 z ,There w You 1-x Cu x Nb 2-y M 1 y THE 7-z M 2 z ,You 1-x Sky x Nb 2-y M 1 y THE 7-z M 2 z ,There w You 1-x Sky x Nb 2-y M 1 y THE 7-z M 2 z 、Overnight、 ·M 1 およびM 2are each at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; M 1 and M. 2 may be the same or different from each other, 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; ·Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Ti 1-x Ce x Nb 2-y M 1 y O 7-z , Li w Ti 1-x Ce x Nb 2-y M 1 y O 7-z , in the formula, M 1 is at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z<1, preferably 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z<0.3; may be selected from the group formed by:

[0032] Optionally, during step (c), the layer is heated to a temperature high enough to remove organic residues by evaporation and / or pyrolysis (called the debinding step).

[0033] More generally, the treatment of step (c) is carried out in several steps or with a continuous temperature ramp, starting with drying, followed optionally by debinding if the deposit contains organic material (this debinding is a heat treatment in air to pyrolyze or calcinate the organic material) and finally a consolidation treatment, which may be only a heat treatment and / or a thermomechanical treatment.

[0034] The formula showing that lithium can exist, i.e. Li w Ti 1-x M 1 x Nb 2-y M 2 y O7, Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Li w Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Cu x Nb2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Ce x Nb 2-y M 1 y O 7-z M 2 z , and Li w Ti 1-x Ce x Nb 2-y M 1 y O 7-z The active materials of Anode A, represented by: are supplied and deposited with w=0 (i.e. without containing lithium): these materials have the ability to insert lithium during the first charge of the battery of which the anode forms a part.

[0035] In step (b), the deposit may be made on both sides of the substrate.

[0036] In a first embodiment, the substrate may be a substrate capable of acting as a current collector. The thickness of the layer after step (c) is advantageously between about 1 μm and about 300 μm, or between 1 μm and 150 μm.

[0037] In a second embodiment, the substrate is an intermediate temporary substrate, such as a polymer film. In this second embodiment, the layer may be separated from the substrate after drying it, preferably before heating it, but at the latest at the end of step (c). The thickness of the layer after step (c) is advantageously between about 5 μm and about 300 μm.

[0038] In two embodiments, when the layer is thick and resistive, it is advantageous to add step (d): (d) a coating of an electronically conductive material is deposited or formed on and within the pores of said porous layer, said electronically conductive material being preferably carbon or an electronically conductive oxide material.

[0039] Step (d) may be carried out by ALD.

[0040] Step (d) may comprise the successive steps of: a layer of a precursor of an electronically conductive material is deposited on and within the pores of said porous layer in step (d1), and in step (d2) the precursor of the electronically conductive material deposited on said porous layer in step (d1) is converted into an electronically conductive material, so that said porous layer has a layer of said electronically conductive material on and within the pores.

[0041] The electronically conductive material may be carbon, in which case step (d1) is advantageously carried out by immersing the porous layer in a liquid phase comprising a carbon-rich compound such as a carbohydrate, and said conversion to an electronically conductive material carried out in step (d2) is in this case a pyrolysis, preferably carried out in an inert atmosphere, more preferably in nitrogen.

[0042] Step (d1) is advantageously carried out by immersing the porous layer in a liquid phase comprising a precursor of said electronically conductive material, in which case said conversion of the precursor of said electronically conductive material in step (d2) into an electronically conductive material is a heat treatment, such as calcination, preferably carried out in air or in an oxidizing atmosphere.

[0043] Advantageously, said precursor of the electronically conductive material is selected from organic salts containing one or more metal elements capable of forming an electronically conductive oxide after a heat treatment, such as calcination, preferably carried out in air or in an oxidizing atmosphere. These metal elements, preferably these metal cations, may advantageously be selected from tin, zinc, indium, gallium, or a mixture of two or three or four of these elements. The organic salt is preferably selected from alcoholates of at least one metal element capable of forming an electronically conductive oxide after a heat treatment, such as calcination, preferably carried out in air or in an oxidizing atmosphere, oxalates of at least one metal element capable of forming an electronically conductive oxide after calcination in air, and acetates of at least one metal element capable of forming an electronically conductive oxide after a heat treatment, such as calcination, preferably carried out in air or in an oxidizing atmosphere.

[0044] Advantageously, the electronically conductive material is preferably tin oxide (SnO2), zinc oxide (ZnO), indium oxide (In2O3), gallium oxide (Ga2O3), mixtures of two of these oxides, for example indium tin oxide, which corresponds to a mixture of indium oxide (In2O3) and tin oxide (SnO2), mixtures of three of these oxides or mixtures of four of these oxides, - doped oxides based on zinc oxide, preferably with gallium (Ga), and / or aluminium (Al), and / or boron (B), and / or beryllium (Be), and / or chromium (Cr), and / or cerium (Ce), and / or titanium (Ti), and / or indium (In), and / or cobalt (Co), and / or nickel (Ni), and / or copper (Cu), and / or manganese (Mn), and / or germanium (Ge) for the doping, - doped oxides based on indium oxide, preferably with tin (Sn), and / or gallium (Ga), and / or chromium (Cr), and / or cerium (Ce), and / or titanium (Ti), and / or indium (In), and / or cobalt (Co), and / or nickel (Ni), and / or copper (Cu), and / or manganese (Mn), and / or germanium (Ge) for the doping, - doped tin oxide, preferably with arsenic (As), and / or fluorine (F), and / or nitrogen (N), and / or niobium (Nb), and / or phosphorus (P), and / or antimony (Sb), and / or aluminium (Al), and / or titanium (Ti), and / or gallium (Ga), and / or chromium (Cr), and / or cerium (Ce), and / or indium (In), and / or cobalt (Co), and / or nickel (Ni), and / or copper (Cu), and / or manganese (Mn), and / or germanium (Ge) for the doping; The material may be an electronically conductive oxide material selected from:

[0045] In general, the primary nanoparticles are advantageously in the form of aggregates or agglomerates, the aggregates or agglomerates having a mean diameter D between 50 nm and 300 nm, preferably between 100 nm and 200 nm. 50 has.

[0046] The porous layer from step (c) is 10 m 2 / g~500m 2 / g.

[0047] The deposition of said coating of electronically conductive material is carried out by the technique of atomic layer deposition (ALD) or by immersion in a liquid phase containing a precursor of said electronically conductive material, followed by conversion of said precursor into the electronically conductive material.

[0048] In said second embodiment, the method for manufacturing a porous anode for a battery uses an intermediate substrate made of a polymer (such as PET), resulting in a so-called "green tape". This green tape is then separated from its substrate, which then forms plates or sheets (hereinafter referred to by the term "plates" regardless of their thickness). These plates can be cut before or after their separation from the intermediate substrate. These plates are then fired to remove the organic constituents. These plates are then sintered to consolidate the nanoparticles until a mesoporous ceramic structure is obtained with a porosity between 25 and 50%. The porous plates obtained in step (c) advantageously have a thickness between 5 μm and 300 μm. It is advantageous to deposit a coating of an electronically conductive material, as described previously.

[0049] In this second embodiment, there is also provided a metal sheet covered on both sides with an intermediate thin layer of nanoparticles, preferably the same as that constituting the electrode plates, said thin layer preferably having a thickness of less than 1 μm.

[0050] This sheet is then inserted between two previously obtained porous electrode plates (for example, two porous anode plates). This assembly is then hot pressed, so that said thin intermediate layer of nanoparticles is deformed by sintering, consolidating the electrode / substrate / electrode assembly to obtain a rigid monoblock assembly. During this sintering, a bond between the electrode layer and the intermediate layer is established by atomic diffusion; this phenomenon is known as diffusion bonding. This assembly is made with two electrode plates of the same polarity (typically between two anodes), and the metal sheet between these two electrode plates of the same polarity establishes a parallel connection between them.

[0051] One of the advantages of the second embodiment is that it allows the use of cheaper substrates such as aluminum or copper foils: indeed, these foils do not withstand the heat treatments used to consolidate the deposited layers, and the fact that they are applied to the electrode plates after their heat treatment also prevents their oxidation.

[0052] This assembly by diffusion bonding may be carried out separately as described above, and the resulting electrode / substrate / electrode subassembly may be used to manufacture a battery. This assembly by diffusion bonding may also be carried out by stacking and hot pressing the entire battery structure, in which case a multi-layer stack is assembled comprising a first porous anode layer according to the invention, its metal substrate, a second porous anode layer according to the invention, a solid electrolyte layer, a first cathode layer, its metal substrate, a second cathode layer, a new solid electrolyte layer, etc.

[0053] More precisely, plates of mesoporous ceramic electrodes (in particular the anode according to the invention) can be applied to both sides of a metal substrate (the same configuration as with the deposits on both sides of the metal substrate). An electrolyte membrane (separator) is then deposited on this electrode / substrate / electrode (in particular anode / substrate / anode). The necessary cuts are then made to produce a battery with several elementary cells, then the subassemblies are stacked (typically from head to tail) and thermocompression is carried out to bond the electrodes to each other at the level of the solid electrolyte.

[0054] Alternatively, a stack may be formed, comprising a first electrode plate, its substrate coated with bonding elements (typically an intermediate layer of nanoparticles of the electrode material to which this intermediate layer is to be welded), a second electrode plate of the same polarity as the first, a solid electrolyte (separator), an electrode plate of the opposite polarity, its substrate coated with bonding elements (typically an intermediate layer of nanoparticles of the electrode material to which this intermediate layer is to be welded), etc. A final hot press is then performed, which is used both to weld the electrodes together on the solid electrolyte and to weld the electrode plates to the current collectors.

[0055] In the two variants presented above, the thermocompression welding is carried out at relatively low temperatures, which is possible due to the very small size of the nanoparticles. As a result, there is no oxidation of the metal layer of the substrate.

[0056] If the electrode layer or plate (the term "electrode plate" - note that the term "plate" also includes "sheet") exhibits sufficient electronic conductivity, a separate current collector may not be necessary. This variation is primarily used for microbatteries and mid-power batteries, and is not the preferred embodiment for batteries with power ratings above 1 mAh.

[0057] In other embodiments of the assembly described below, a conductive adhesive (filled with graphite) or a sol-gel deposit filled with conductive particles, or a metal strip preferably having a low melting point (e.g., aluminum) is used, and during thermomechanical processing (hot pressing), a metal foil can be deformed by flow or used to form this seam between the plates.

[0058] A second subject of the invention is a porous anode for a lithium-ion battery designed to have a capacity of more than 1 mAh, comprising a porous layer with a porosity between 25% and 50% by volume, preferably between 28% and 43% by volume, and even more preferably between 30% and 40% by volume, The porous layer is - pores with an average diameter of less than 50 nm, - a porous network of material A, optionally comprising a coating of an electronically conductive material on and within the pores forming said porous network; The present invention is characterized in that it comprises The material A is preferably selected from niobium oxide and mixed oxides of niobium with titanium, germanium, cerium, lanthanum, copper or tungsten, NbO 5-δ , Nb 18 W 16 O93-δ , Nb 16 W5O 55-δ , where 0 ≤ x < 1 and 0 ≤ δ ≤ 2; ·TiNbO 7-δ , Ti 1-x M 1 x Nb 2-y M 2 y O 7-δ , Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7-δ , where M 1 and M. 2 are at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, and Sn, and M 1 and M. 2 may be the same or different from each other, and 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and 0≦δ≦0.3; ·Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , in the formula, M 1 and M. 2 are each at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, and Sn; M1 and M. 2 may be the same or different from each other, M 3 is at least one halogen; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; ·TiNbO 7-z M 3 z , Li w TiNbO 7-z M 3 z , where M 3 is at least one halogen, preferably at least one halogen selected from F, Cl, Br, I, or mixtures thereof, and 0 <z≦0.3である; ·Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Ti 1-x Ce x Nb 2-y M 1 y O 7-z , Li w Ti 1-x Ce x Nb 2-y M 1 y O 7-z , in the formula, M 1 and M. 2 is at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z<1, preferably 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3 (preferably z<0.3); ·Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x Ce x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Ce x Nb2-y M 1 y O 7-z M 2 z , in the formula, M 1 and M. 2 are each at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; M 1 and M. 2 may be the same or different from each other, 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; and wherein the compound is selected from the group formed by said anode being obtainable by the method according to the invention, It is a porous anode.

[0059] A third subject matter is a method for producing a battery, preferably a lithium-ion battery, by implementing the method for producing a porous anode according to the invention or by using a porous anode according to the invention.

[0060] Such a method is for manufacturing a battery comprising at least one porous anode according to the invention, at least one separator and at least one porous cathode, comprising: (a) a first substrate and a second substrate are provided; - a first colloidal suspension or paste is provided comprising aggregates or agglomerates of monodisperse primary nanoparticles of at least one active material of the anode A, the aggregates or agglomerates having an average primary diameter D 50 is between 2 and 100 nm, preferably between 2 and 60 nm, and the aggregates or agglomerates have an average diameter D 50 having The material A is preferably selected from niobium oxide and mixed oxides of niobium with titanium, germanium, cerium, lanthanum, copper or tungsten, NbO 5-δ , Nb 18 W 16 O 93-δ , Nb 16 W5O 55-δ , where 0 ≤ x < 1 and 0 ≤ δ ≤ 2; ·TiNbO 7-δ , Ti 1-x M 1 x Nb 2-y M 2 y O 7-δ , Li w Ti 1-x M 1 x Nb 2-y M 2 y O7, where M 1 and M. 2 Each of M is at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, and Sn, and may be the same or different from each other. 1 and M. 2 , 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and 0≦δ≦0.3; ·Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , in the formula, M 1 and M. 2are each at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, and Sn; M 1 and M. 2 may be the same or different from each other, M 3 is at least one halogen; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; ·TiNbO 7-z M 3 z , Li w TiNbO 7-z M 3 z , where M 3 is at least one halogen, preferably at least one halogen selected from F, Cl, Br, I, or mixtures thereof, and 0 <z≦0.3である; ·Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Ti 1-x Ce x Nb 2-y M 1 y O 7-z , Li w Ti 1-x Ce x Nb 2-y M 1 y O 7-z , in the formula, M 1is at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z<1, preferably 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z<0.3; ·Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x Ce x Nb 2-y M 1y O 7-z M 2 z , Li w Ti 1-x Ce x Nb 2-y M 1 y O 7-z M 2 z , in the formula, M 1 and M. 2 are each at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; M, which may be the same or different 1 and M. 2 , 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; and wherein the selected group is formed by Bearing in mind that the first and / or second substrate may be a substrate capable of functioning as a current collector or an intermediate substrate, - a second colloidal suspension is provided comprising aggregates or agglomerates of monodisperse primary nanoparticles of at least one cathode active material C, the aggregates or agglomerates having an average primary diameter D 50 is between 2 nm and 100 nm, preferably between 2 nm and 60 nm, and the aggregates or agglomerates have a mean diameter D between 50 nm and 300 nm (preferably between 100 nm and 200 nm). 50 having - a third colloidal suspension is provided, comprising aggregates or agglomerates of nanoparticles of at least one inorganic material E, which is preferably an electrical insulator, having a mean primary diameter D 50 is between 2 nm and 100 nm, preferably between 2 nm and 60 nm, and the aggregates or agglomerates have a mean diameter D between 50 nm and 300 nm (preferably between 100 nm and 200 nm). 50 having (b) depositing an anode layer from the first colloidal suspension provided in step (a) on at least one side of the first substrate and a cathode layer from the second colloidal suspension provided in step (a) on at least one side of the second substrate, preferably by a method selected from the group consisting of a printing method selected from electrophoresis, extrusion, preferably inkjet printing and flexographic printing, and a coating method preferably selected from roll coating, curtain coating, doctor blade coating, coating by extrusion through a slot die, dip coating; (c) drying the anode and cathode layers obtained in step (b), optionally after separating said layers from their intermediate substrate, and consolidating each layer by pressing and / or heating, to obtain a porous, preferably mesoporous, inorganic anode layer and a porous, preferably mesoporous, inorganic cathode layer, respectively; (d) optionally, a coating of electronically conductive material is deposited on and within the pores of said porous anode and / or cathode layers to also form said porous anode and porous cathode; (e) depositing a porous inorganic layer from the third colloidal suspension provided in step (a) on said porous anode and / or said porous cathode obtained in step (c) or (d) by a technique selected from the group comprising electrophoresis, extrusion, printing methods preferably selected from inkjet printing and flexographic printing, and preferably roll coating, curtain coating, doctor blade coating, coating by extrusion through a slot die, dip coating, (f) the porous inorganic layer of the structure obtained in step (e) is dried, preferably under air flow, and subjected to a heat treatment at a temperature above 130° C., preferably between about 300° C. and about 600° C., bearing in mind that, if necessary, before carrying out the heat treatment, the layer separated from its intermediate substrate is pressed onto a metal sheet capable of acting as a current collector; (g) the porous anode obtained in step d) or e) is stacked successively opposite the porous cathode obtained in step d) or e), the stack obtained being understood to comprise at least one porous inorganic layer as obtained in step e) forming said separator, (h) subjecting the stack obtained in step (g) to a hot pressing treatment at a temperature between 120° C. and 600° C. to obtain a battery comprising at least one porous anode, at least one separator and at least one porous cathode. The method is characterized in that

[0061] The heat treatment in step (h) is carried out after deposition on the electrode of the membrane separator. The product from step (h) can then be impregnated with an ion-conducting polymer or a polymer made ion-conducting, or even with a liquid electrolyte containing at least one lithium salt, which advantageously comprises: an electrolyte consisting of at least one aprotic solvent and at least one lithium salt; an electrolyte consisting of at least one ionic liquid and at least one lithium salt; a mixture of at least one aprotic solvent, at least one ionic liquid and at least one lithium salt, a polymer that has been made ionically conductive by the addition of at least one lithium salt, and Polymers that are made ionically conductive by adding a liquid electrolyte either in the polymer phase or in the mesoporous structure The compound is selected from the group formed by:

[0062] These fabrication methods allow the production of all-solid-state batteries with fine ceramic separators that are very well impregnated with ionic liquids and are resistant to high temperatures.

[0063] A further subject of the invention is a lithium-ion battery with a capacity of more than 1 mAh obtainable by the method according to the invention, the battery then comprising an anode according to the invention or an anode obtainable by the method according to the invention, the anode advantageously having a mass capacity of more than 200 mAh / g, preferably more than 250 mAh / g.

[0064] A final subject of the invention is the use of a battery according to the invention at temperatures below -10°C and / or above 50°C, preferably below -20°C and / or above 60°C, even more preferably below -30°C and / or above 70°C.

[0065] In an advantageous embodiment of the invention, the battery has a lower anode surface capacity than the cathode surface capacity, which improves the temperature stability of the battery.

[0066] In general, the creation of a completely solid sintered multilayer structure presents many problems. It requires heating to high temperatures to carry out the sintering, which can degrade the electrode material and cause interdiffusion at the interfaces. According to one of its essential features, the method according to the invention uses nanoparticles that allow the sintering temperature to be reduced. Furthermore, advantageously, partial sintering can be carried out to obtain a mesoporous structure. Furthermore, this sintering can be carried out on the electrode layers or plates before assembly with the separator, thereby avoiding the presence of ceramic layers of different materials in contact during sintering. For the separator, it is advantageous to choose a material that has a relatively low melting point and is inert to the contact of the electrodes, in order to be able to carry out this assembly at a relatively low temperature. [Brief description of the drawings]

[0067] [Figure 1] 1 shows discharge curves obtained with a Ti0.95Ge0.05Nb2O7 anode according to the present invention for two different regions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0068] 1.Definition In the context of this document, the size of a particle is defined by its largest dimension. A "nanoparticle" is defined as a nanometer-sized particle or object having at least one of its dimensions less than or equal to 100 nm.

[0069] In the context of this document, the term "electronically conducting oxide" is defined as electronically conducting oxides and electronically semiconducting oxides.

[0070] In the context of this document, an electronically insulating material or layer, preferably an electronically insulating and ionically conductive layer, is 5 A material or layer that has an electrical resistivity (resistance to the passage of electrons) greater than Ω·cm. "Ionic liquids" refer to liquid salts that can transport electricity, but differ from all molten salts in that they have a melting temperature below 100 °C. Some of these salts remain liquid at ambient temperature and do not solidify even at very low temperatures. Such salts are called "ionic liquids at ambient temperature".

[0071] The term "mesoporous material" refers to a solid having in its structure pores called "mesopores" with a size intermediate between the size of micropores (width less than 2 nm) and the size of macropores (width more than 50 nm), i.e. between 2 nm and 50 nm. This terminology corresponds to the terminology adopted by IUPAC (International Union for Pure and Applied Chemistry), which is a reference for the skilled person. Thus, the term "nanopores" is not used here, even if the mesopores as defined above have nanometer dimensions within the meaning of the definition of nanoparticles, bearing in mind that pores with a size smaller than that of mesopores are called "micropores" by the skilled person.

[0072] An explanation of the concept of porosity (and the terminology explained above) is given in the article ''Texture des materiaux pulverulents or poreux'' (''Texture of powdered or porous materials'') by F. Rouquerol et al., published in the collection ''Techniques de l'Ingenieur'' (''Engineering techniques''), Analysis and Characterisation, section P1050, which also describes techniques to characterise porosity, in particular the BET method.

[0073] In the sense of the present invention, the term "mesoporous layer" refers to a layer having mesopores. As explained below, in these layers the mesopores contribute significantly to the total pore volume, which is reflected in the expression "mesoporous layer having more than X% by volume of mesoporous porosity" used in the following description, X% being preferably more than 25%, preferentially more than 30% and even more preferably between 30 and 50% of the total volume of the layer.

[0074] The term "aggregate" is used to describe a loosely bound collection of primary particles according to the IUPAC definition. In this case, these primary particles are nanoparticles with a diameter that can be determined by transmission electron microscopy. Aggregates of primary nanoparticles that are aggregated can usually be broken down in suspension (i.e., reduced to primary nanoparticles) in the liquid phase from the effect of ultrasound by techniques known to those skilled in the art.

[0075] The term "agglomerate" is defined as a tightly bound collection of primary particles or aggregates according to the IUPAC definition.

[0076] In the sense of the present invention, the term "electrolyte layer" refers to a layer in an electrochemical device, which device is able to function according to its purpose. For example, if said electrochemical device is a secondary lithium ion battery, the term "electrolyte layer" refers to a "porous inorganic layer" impregnated with a carrier phase for lithium ions. The electrolyte layer is an ion conductor but electronically insulating.

[0077] Said porous inorganic layer in an electrochemical device is also referred to herein as a "separator", in accordance with the terminology used by those skilled in the art.

[0078] According to the present invention, the "porous inorganic layer", which is preferably mesoporous, may be electrophoretically deposited by a dip-coating method, hereinafter referred to as "dip-coating", by an ink-jet printing method, hereinafter referred to as "ink-jet printing", by "roll-coating", by "curtain-coating" or by "doctor-blade-coating", which may be deposited from a suspension of nanoparticle aggregates or agglomerates, preferably from a concentrated suspension containing agglomerates of nanoparticles.

[0079] 2. Preparation of Nanopowder Suspension In the context of the present invention, monodisperse crystallized nanopowders with a primary particle size of less than 100 nm are preferably used for the electrode layer and the separator layer. This promotes necking between the primary particles (whether in agglomerated form or not) during the consolidation process. Consolidation can then be carried out at a relatively low temperature if the primary particles are already in a crystallized state, keeping in mind that the purpose of this process is no longer to recrystallize the primary particles. Some chemical compositions require the use of specific synthesis methods to obtain a population of monodisperse crystallized nanoparticles.

[0080] Generally, TNO (TiNb2O7) type compositions have a very low electronic conductivity. In order to deliver high power in a battery, the particles need to be very small. Furthermore, as explained below, to compensate for this low electronic conductivity of the anode material, the mesoporous network is advantageously coated with a thin layer of an electronically conductive material, and a thin layer of graphitic carbon is used for this purpose (not diamond-like carbon).

[0081] It is known that TNO (TiNb2O7) type particles can be hydrothermally synthesized with a size distribution of about 50 nm to about 300 nm, but this size is difficult to control and the distribution is wide. This synthesis results in amorphous particles, which then need to be crystallized by heat treatment at high temperatures, for example about 1000 °C for about 30 minutes. During this crystallization, the particles can grow in an uncontrolled manner, which leads to a wide distribution of sizes. Alternatively, there are solid-phase synthesis methods that also require high-temperature treatments to homogenize the chemical composition.

[0082] In the context of the present invention, it is preferred to use primary nanoparticles, whether agglomerated or not, having a size of less than 100 nm, preferably less than 60 nm, even more preferably less than 40 nm. Such nanoparticles can be obtained in various ways.

[0083] According to one method, salts, complexes or alcoholates (such as ethanolates) of the cations of the metal elements that will enter into the composition of the desired phase are mixed to obtain a completely homogeneous distribution on the atomic scale, and polymers are used to fix this distribution of molecules, ions or complexes containing the metal elements. These polymers are then removed by heat treatment, leaving only the inorganic components on the atomic scale, of which a simple calcination at a relatively low temperature will make it possible to obtain the desired crystalline phase on the nanoparticle scale. It is possible to add organic materials that can strongly outgas during the heat treatment stage and that contribute to obtaining mesoporous agglomerates.

[0084] An example of such a synthesis is the "Pecini process", a sol-gel type process, in which cations of the desired phase (in our case, for example, Nb, Ti, etc.) are complexed by organic molecules (such as citric acid or EDTA (ethylenediaminetetraacetic acid)) and introduced into a polymer matrix (for example, polyhydric alcohols such as polyethylene glycol or polyvinyl alcohol). This results in a very homogeneous distribution of the complexed and diluted cations. The polymer and the complexed organic molecules are subsequently eliminated by pyrolysis, leading to the formation of the target inorganic oxide. Calcination at about 700 ° C makes it possible to obtain crystallized nanoparticles. This process makes it possible to adjust the size of the particles, which then reduces the concentration of the cations in the reduced polymer matrix.

[0085] As an example, to obtain a suspension of cathode material particles, LiMn2O4 powder consisting of clusters of nanoparticles can be synthesized using the Pechini process described in the paper ''Synthesis and Electrochemical Studies of Spinel Phase LiMn2O4 Cathode Materials Prepared by the Pechini Process'', W. Liu, GC Farrington, F. Chaput, B. Dunn, J. Electrochem. Soc., vol. 143, No. 3, 1996. After a calcination step at 600 °C, the powder contains clusters with a size typically between 50 nm and 100 nm, and the size of the crystallized primary nanoparticles is typically between 10 nm and 30 nm, depending on the synthesis conditions.

[0086] A particularly preferred anode material is Li w Ti 1-x Ge x Nb 2-y M1 y O 7-z M 3 z wherein M 1 is at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn, and 0 ≦ w ≦ 5, 0 ≦ x ≦ 1, 0 ≦ y ≦ 2, and z ≦ 0.3. M 3 is at least one halogen. When germanium is present in the anode composition, the resistance of the battery decreases and its output increases, so preferably 0 < x ≦ 1, more preferably 0.1 ≦ x ≦ 1.

[0087] It should be noted that the redox characteristics of germanium enable this compound to obtain a lithium insertion behavior that is almost the same as that of a similar compound without germanium. Ge 4+ / Ge 3+ The redox potential of the ion is Ti 4+ / Ti 3+ Even when slightly lower than the redox potential of the pair, this potential maintains a height sufficient to avoid lithium deposition (plating) during recharge and enables an increase in the energy density of the anode.

[0088] Other active anode materials A are particularly preferred, and these are Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x La x Nb 2-y M 1 y O7-z M 2 z , Li w Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x Ce x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Ce x Nb 2-y M 1 y O 7-z M 2 z is a material of the type M 1 and M. 2 are each at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; M, which may be the same or different 1 and M. 2 , 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3.

[0089] For each of these anode active materials, when germanium, cerium, lanthanum, or copper is present in the composition of the anode, the cycle performance of the battery is improved, so 0 < x ≦ 1 is preferable, and 0.1 ≦ x ≦ 1 is even more preferable.

[0090] Li w Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z Regarding this, when copper is present in this anode active material, it is also possible to increase the battery output, so 0 < x ≦ 1 is preferable, and 0.1 ≦ x ≦ 1 is even more preferable.

[0091] A battery having a mesoporous anode made from this material can be recharged very rapidly and has a very good volumetric energy density that is greater than the volumetric energy density obtained with a conventional Li4Ti5O 12 anode.

[0092] According to the present invention, the cathode material is preferably LiCoPO4; LiMn 1.5 Ni 0.5 O4; LiFe x Co 1-x PO4 (where 0 < x < 1); LiNi 1 / X Co 1 / y Mn 1 / Z O2, where x + y + z = 10; Li 1.2 Ni 0.13 Mn 0.54 Co 0.13 O2; LiMn 1.5 Ni 0.5-x X x O4, where X is selected from Al, Fe, Cr, Co, Rh, Nd, Sc, Y, Lu, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, where 0 < x < 0.1; LiNi 0.8 Co 0.15 Al 0.05O2; Li2MPO4F (where M = Fe, Co, Ni, or a mixture of these different elements); LiMPO4F (where M = V, Fe, Ti, or a mixture of these different elements); LiMSO4F (where M = Fe, Co, Ni, Mn, Zn, Mg), LiNi 1 / x Mn 1 / y Co 1 / z O2, where x+y+z=10; LiCoO2.

[0093] For high capacity cathodes, especially LiNi 1 / x Mn 1 / y Co 1 / z O2, where x+y+z=10, LiNi 0.8 Co 0.15 Al 0.05 O2, and LiCoO2 are preferred.

[0094] For example, LiNi x Mn y Co z O2 (also known as NMC) may be used preferably with x+y+z=1, even more preferably with x:y:z=4:3:3 (the material known as NMC433).

[0095] 3. Deposition of layers and their consolidation Generally, a layer of the nanoparticle suspension is deposited on the substrate by any suitable technique, in particular by a method selected from the group comprising electrophoresis, extrusion, printing methods, preferably inkjet printing or flexographic printing, coating methods, preferably doctor blade coating, roll coating, curtain coating, dip coating or slot die passage. The suspension is typically in the form of an ink, i.e. a fairly fluid liquid, but can also have a paste-like consistency. The deposition technique and method must be adapted to the viscosity of the suspension and vice versa.

[0096] The deposited layers are then dried. They are then consolidated to obtain the desired ceramic mesoporous structure. This consolidation is described below. It involves a heat treatment and possibly a thermomechanical treatment, typically thermocompression. During this thermomechanical treatment, the electrode layer is freed of organic components and residues (such as the liquid phase of the nanoparticle suspension and surfactant products) and becomes an inorganic (ceramic) layer. Consolidation of the plate is preferably carried out after its separation from the intermediate substrate, since the latter may deteriorate during this treatment.

[0097] The deposition of the layers, their drying, and compaction can give rise to certain problems which will now be discussed. These problems are in part related to the fact that shrinkage occurs during compaction of the layers, which generates internal stresses.

[0098] According to a first embodiment, the electrode layers are each deposited on a substrate capable of acting as a current collector. Metal sheets (i.e. laminated metal sheets) are preferred for this purpose. A layer containing a suspension of nanoparticles or nanoparticle agglomerates can be deposited on both sides by the deposition techniques previously indicated.

[0099] It is observed that if one wishes to increase the thickness of the electrode, the shrinkage caused by compaction can lead to cracking of the layer or to shear stresses at the interface between the substrate (which has fixed dimensions) and the ceramic electrode, which, when they exceed a threshold level, cause the layer to detach from its substrate.

[0100] To avoid this phenomenon, it is preferable to increase the thickness of the electrode by successive deposition-sintering operations. This first variant of the first embodiment of depositing layers gives good results, but is not very productive. Alternatively, in a second variant, layers with a greater thickness are deposited on both sides of a perforated substrate. The perforations must have a sufficient diameter for the two layers, front and back, to be in contact at the perforations. Thus, during consolidation, the nanoparticles and / or agglomerates of nanoparticles of the electrode material that are in contact through the perforations of the substrate weld together to form attachment points (weld points between the deposits on both sides). This limits the loss of adhesion of the layer to the substrate during the consolidation step.

[0101] According to a second embodiment, the electrode layers are not deposited on a substrate that can act as a current collector, but on a temporary intermediate substrate. In particular, rather thick layers (green sheets) can be deposited from a more concentrated suspension (i.e. less fluid, preferably pasty) of nanoparticles and / or nanoparticle agglomerates. These thick layers are deposited, for example, by coating methods with reference to doctor blade or tape casting techniques. Said intermediate substrate can be a polymer sheet, for example polyethylene terephthalate, abbreviated to PET. During drying, these layers do not crack. For consolidation by heat treatment (preferably already to dry them), they can be detached from their substrate; as a result, so-called "green" electrode plates are obtained, which become free-standing mesoporous ceramic plates after a calcination heat treatment and partial sintering.

[0102] A three-layer stack is then formed, i.e. two electrode plates with the same polarity separated by a metal sheet that can act as a current collector. This stack is then assembled by a thermomechanical process that preferably includes pressing and heat treatment simultaneously. In one variant, to promote the bond between the ceramic plate and the metal sheet, the interface can be coated with a layer that allows for an electronically conductive bond. This layer can be a sol-gel layer (preferably of the type that allows the chemical composition of the electrode to be achieved after heat treatment) optionally loaded with particles of an electronically conductive material, which will create a ceramic bond between the mesoporous electrode and the metal sheet. This layer can also be formed by a thin layer of unsintered electrode nanoparticles, or a thin layer of a conductive adhesive (e.g. loaded with graphite particles), or even a metal layer of a metal with a low melting point.

[0103] Said metal sheet is preferably a laminated sheet, i.e. obtained by lamination. Lamination may optionally be followed by a final annealing, which, according to metallurgical terminology, may be a softening (total or partial) or a recrystallization annealing. It is also possible to use electrochemically deposited sheets, for example electroplated copper sheets or electroplated nickel sheets.

[0104] In either case, the mesoporous ceramic electrodes, without an organic binder, can be disposed on either side of a metal substrate used as an electron current collector.

[0105] In one variation of the method according to the invention, the battery is made without the use of metal current collectors. This is possible if the electrode plates are electronically conductive enough to ensure the passage of electrons across the ends of the electrodes. If the electrode material has an inherently very high electronic conductivity (LiCoO2 or Nb 16 W5O 55 Sufficient electronic conductivity can be observed either when the mesoporous surface is coated with an electronically conductive layer (such as the case of materials with a SiO 2 SiO 2 layer) or when the mesoporous surface is coated with an electronically conductive layer.

[0106] 4. Deposition of a thin layer of electronic conductor This step is optional. In fact, depending on the desired output of the electrode (which also affects its thickness) and the conductivity of the electrode material, this treatment may or may not be necessary to improve the conductivity of the electrode. For example, TNO (titanium niobium oxide) is generally less conductive than NWO (niobium tungsten oxide), and therefore, for the same thickness, it is the anode layer of NWO that requires more of this deposition of a thin electronically conductive film. Similarly, for the same material, a thicker electrode layer will require more of this thin electronically conductive film than a thinner electrode layer.

[0107] The anode materials (more particularly titanium oxide, niobium oxide and mixed oxides of titanium and niobium, in particular TiNb2O7, abbreviated TNO) and cathode materials used in the context of the present invention are poor electronic conductors. Batteries containing them therefore have a high series resistance, which implies a resistive loss of energy, even more so the thicker the electrode. According to the present invention, nanolayers of electronically conductive material are deposited in the mesoporous network, i.e. inside the pores, to ensure good electronic conductivity of the electrode. This need to increase the conductivity is greater the thicker the deposit. It is therefore possible to have high power, thick electrodes with low series resistance.

[0108] To address this problem, in accordance with an optional feature of the invention, a coating of electronically conductive material is deposited on and within the pores of said porous layer of anode material.

[0109] Indeed, as explained above, during consolidation of the layer anode material, the nanoparticles of the anode material naturally "weld" to each other to generate a porous, rigid three-dimensional structure without any organic binder, and this porous layer, preferably a mesoporous layer, is perfectly suitable for the application of surface treatments by gas or liquid means, which penetrate into the depth of the open porous structure of the layer.

[0110] Highly advantageously, this deposition, if carried out, is carried out by a technique that allows a coating (also called "conformal deposition"), i.e. a deposition that faithfully reproduces the atomic topography of the substrate to which it is applied, penetrating deep into the open porous network of the layer. Said electronically conductive material may be carbon.

[0111] ALD techniques (atomic layer deposition) or CSD (chemical solution deposition), known per se, may be suitable. These may be applied to the electrodes after their manufacture, before and / or after the deposition of the separator particles, as well as before and / or after the assembly of the cell. The ALD deposition techniques are carried out layer by layer in a cyclical manner and make it possible to form a coating that closely reproduces the topography of the substrate, the coating covering the entire surface of the electrode. This coating typically has a thickness between 1 nm and 5 nm.

[0112] Deposition by ALD is typically carried out at temperatures between 100 °C and 300 °C. It is important that the layers are free of organic materials; they must not contain any organic binders, and any residues of the stabilizing binders used to stabilize the suspension must have been removed by purification of the suspension and / or during heat treatment of the layer after drying. In fact, at the temperatures of ALD deposition, organic materials forming organic binders (e.g. polymers contained in the casting electrodes of ink tapes) run the risk of decomposing and contaminating the ALD reactor. Moreover, the presence of residual polymers in contact with the electrode active material particles prevents the ALD coating from coating the entire particle surface, thereby reducing its effectiveness.

[0113] The technique of CSD deposition also makes it possible to form a coating with a precursor of an electronically conductive material that faithfully reproduces the topography of the substrate, covering the entire surface of the electrode. This coating typically has a thickness of less than 5 nm, preferably between 1 nm and 5 nm. It then needs to be converted into an electronically conductive material. In the case of carbon precursors, this is carried out by pyrolysis, preferably in an inert gas (such as nitrogen).

[0114] The layer of electronically conductive material can be very advantageously formed by immersion in a liquid phase containing a precursor of said electronically conductive material, followed by a heat treatment to convert said precursor of said electronically conductive material into an electronically conductive material. This method is simple, fast, easy to implement and less expensive than ALD atomic layer deposition techniques. Advantageously, said precursor of electronically conductive material is selected from organic salts containing one or more metal elements capable of forming an electronically conductive oxide after a heat treatment, such as a calcination, preferably carried out in air or in an oxidizing atmosphere. These metal elements, preferably metal cations, can be advantageously selected from tin, zinc, indium, gallium, or a mixture of two or three or four of these elements. The organic salt is preferably selected from an alcoholate of at least one metal cation capable of forming an electronically conductive oxide after a heat treatment, such as calcination, preferably carried out in air or in an oxidizing atmosphere, an oxalate of at least one metal cation capable of forming an electronically conductive oxide after a heat treatment, such as calcination, preferably carried out in air or in an oxidizing atmosphere, and an acetate of at least one metal cation capable of forming an electronically conductive oxide after a heat treatment, such as calcination, preferably carried out in air or in an oxidizing atmosphere.

[0115] Advantageously, the electronically conductive material is preferably tin oxide (SnO2), zinc oxide (ZnO), indium oxide (In2O3), gallium oxide (Ga2O3), mixtures of two of these oxides, for example indium tin oxide, which corresponds to a mixture of indium oxide (In2O3) and tin oxide (SnO2), mixtures of three of these oxides or mixtures of four of these oxides, - doped oxides based on zinc oxide, preferably with gallium (Ga), and / or aluminium (Al), and / or boron (B), and / or beryllium (Be), and / or chromium (Cr), and / or cerium (Ce), and / or titanium (Ti), and / or indium (In), and / or cobalt (Co), and / or nickel (Ni), and / or copper (Cu), and / or manganese (Mn), and / or germanium (Ge) for the doping, - doped oxides based on indium oxide, preferably with tin (Sn), and / or gallium (Ga), and / or chromium (Cr), and / or cerium (Ce), and / or titanium (Ti), and / or indium (In), and / or cobalt (Co), and / or nickel (Ni), and / or copper (Cu), and / or manganese (Mn), and / or germanium (Ge) for the doping, - doped tin oxide, preferably with arsenic (As), and / or fluorine (F), and / or nitrogen (N), and / or niobium (Nb), and / or phosphorus (P), and / or antimony (Sb), and / or aluminium (Al), and / or titanium (Ti), and / or gallium (Ga), and / or chromium (Cr), and / or cerium (Ce), and / or indium (In), and / or cobalt (Co), and / or nickel (Ni), and / or copper (Cu), and / or manganese (Mn), and / or germanium (Ge) for the doping; The material may be an electronically conductive oxide material selected from:

[0116] To obtain a layer of an electronically conductive material from alcoholates, oxalates or acetates, preferably an electronically conductive oxide material, the porous layer can be immersed in a rich solution of the desired electronically conductive material precursor. The electrode is then dried and subjected to a heat treatment, preferably in air or in an oxidizing atmosphere, at a temperature sufficient to pyrolyze the precursor of the electronically conductive material of interest. Thus, a coating is formed from an electronically conductive material, distributed completely over the entire inner surface of the electrode, preferably a coating of an electronically conductive oxide material, more preferably made of SnO2, ZnO, In2O3, Ga2O3 or indium tin oxide.

[0117] The presence of an electronically conductive coating in the form of an oxide on and in the pores of the porous layer instead of the carbon coating gives the electrode good electrochemical performance at high temperatures and significantly increases its stability. The fact of using an electronically conductive coating in the form of an oxide instead of a carbon coating gives, among other things, a better electronic conduction to the final electrode. In fact, the presence of this electronically conductive oxide layer on and in the pores of the porous layer or plate makes it possible, especially based on the fact that the conductive coating is in the form of an oxide, to improve the final properties of the electrode, in particular its voltage resistance, its temperature resistance during sintering, to improve the electrochemical stability of the electrode, in particular when it is in contact with the electrolyte, and to reduce the polarization resistance of the electrode even when it is thick. In the case of thick electrodes and / or when the resistance of the active material of the porous layer is too strong, it is particularly advantageous to use an electronically conductive coating in the form of an oxide, in particular of the type In2O3, SnO2, ZnO, Ga2O3 or a mixture of one or more of these oxides, on and in the pores of the porous layer of the electrode active material.

[0118] The electrodes according to the invention are porous, preferably mesoporous, and have a large specific surface area. Increasing the specific surface area of ​​the electrode increases the exchange surface and, consequently, the power output of the battery, but also accelerates parasitic reactions. The presence of these electronically conductive coatings in the form of oxides on and within the pores of the porous layer will block these parasitic reactions.

[0119] Furthermore, based on the very large specific surface area, the effect of these electronically conductive coatings on the electronic conductivity of the electrode will be much more pronounced than in the case of conventional electrodes with a smaller specific surface area, even if the conductive coating deposited is thin. These electronically conductive coatings deposited on and within the pores of the porous layer provide the electrode with excellent electronic conductivity.

[0120] It is essentially a synergistic combination of a porous layer or plate made from an electrode active material and an electronically conductive coating in the form of an oxide placed on and within the pores of said porous layer or plate, which improves the final properties of the electrode, making it possible in particular to obtain thick electrodes without increasing their internal resistance.

[0121] Furthermore, the formation of an electronically conductive coating in the form of an oxide on and within the pores of a porous layer can be achieved more easily and cheaply than a carbon coating. Indeed, in the case of an electronically conductive material coating in the form of an oxide, the conversion of the precursor of the electronically conductive material into the electronically conductive coating does not have to be carried out in an inert atmosphere, as is the case with carbon coatings.

[0122] In this variant of depositing a nanolayer of electronically conductive material, the diameter D of the primary particles of the electrode material is limited to prevent the conductive layer from clogging the open porosity of the electrode layer. 50 is preferably at least 10 nm.

[0123] When depositing free-standing electrode plates, this treatment may be carried out on the mesoporous ceramic plate prior to bonding to the current collector.

[0124] 5. Layer Material Selection To obtain high performance batteries, their mass capacity and voltage must be optimized, which may mean that there are limitations on the choice of different materials that must be compatible with each other and stable in the potential conditions in which the battery will operate.

[0125] In this section, the cathode materials are discussed. The anode materials have been presented above and are oxide formulations containing niobium. These anode materials have mass capacities of over 160 mAh / g and lithium insertion voltages of over 0.5 V / Li, allowing for rapid recharging without the risk of lithium plating. Furthermore, these anode materials used by the present invention do not have significant volumetric variations during charging and discharging conditions, so they can be used in fully solid-state cells.

[0126] As regards the cathode material, in the method for producing a battery according to the invention, as presented in the previous "Subject Matter" section, in a first embodiment, when the porous cathode has a mass capacity of more than 120 mAh / g and operates at a voltage of less than 4.5 V: said cathode active material C is advantageously LiCoO2, LiNi 1 / x Co 1 / y Mn 1 / z O2, where x+y+z=10, Li 1.2 Ni 0.13 Mn 0.54 Co 0.13 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, Li2FePO4F, LiMSO4F, where M=Fe, Co, Ni, Mn, Zn, Mg or a mixture of these different elements; a cathode plate in which the cathode layer is initially deposited on an intermediate substrate and heat treated after it has been separated from its initial substrate and before it is brought into contact with a substrate capable of acting as a current collector, said first and second substrates being selected from the group formed by the metals Cu, Al, stainless steel, Mo, W, Ta, Ti, Cr, Ni and alloys formed by at least one of these elements, bearing in mind that said plate can be plated with a low melting substrate such as a sheet of aluminium, The method is more particularly characterized as follows: in step (i), between steps (f) and (g), the structure obtained after step (f) or after step (h), said battery is an electrolyte consisting of at least one aprotic solvent and at least one lithium salt; an electrolyte consisting of at least one ionic liquid and at least one lithium salt; a mixture of at least one aprotic solvent, at least one ionic liquid and at least one lithium salt, a polymer that has been made ionically conductive by the addition of at least one lithium salt, and Polymers that are made ionically conductive by adding a liquid electrolyte either in the polymer phase or in the mesoporous structure an electrolyte that is electrochemically stable up to at least 4.5 V, selected from the group formed by Even more preferably, N-Butyl-N-methyl-pyrrolidinium 4,5-dicyano-2-(trifluoromethyl)imidazole (Pyr 14 TDI) and an electrolyte containing a lithium salt of the LiTDI type; An electrolyte containing 1-methyl-3-propylimidazolium, 4,5-dicyano-2-(trifluoromethyl)imidazolide (PMIM-TDI), and lithium 4,5-dicyano-2-(trifluoromethyl)imidazolide (LiTDI) The electrolyte is impregnated with an electrolyte selected from the group formed by

[0127] The use of conductive adhesives or electronically deposited conductive layers deposited by sol-gel methods can protect metal substrates from corrosion, in which case first and / or second substrates made of less noble metals than those mentioned, in particular aluminum and copper, can be used.

[0128] The RTIL used is a combination of cationic and anionic groups. The cation is preferably selected from the group formed by the following cationic compounds and families of cationic compounds: imidazolium (such as cation 1-pentyl-3-methylimidazolium, abbreviated PMIM), ammonium, pyrrolidinum, and / or the anion is preferably selected from the group formed by the following anionic compounds and families of anionic compounds: bis(trifluoromethanesulfonyl)imide, bis(trifluorosulfonyl)imide, trifluoromethylsulfonate, tetrafluoroborate ... orate, hexafluorophosphate, 4,5-dicyano-2-(trifluoromethyl)imidazolium (abbreviated as TDI), bis(oxlate)borate (abbreviated as BOB), oxalyldifluoroborate (abbreviated as DFOB), bis(mandelato)borate (abbreviated as BMB), and bis(perfluoropinacolato)borate (abbreviated as BFPPB).

[0129] As described in more detail in the following paragraphs, in a second embodiment of the method, after step (h), in step (i), the battery is an electrolyte consisting of at least one aprotic solvent and at least one lithium salt; an electrolyte consisting of at least one ionic liquid and at least one lithium salt; a mixture of at least one aprotic solvent, at least one ionic liquid and at least one lithium salt, a polymer that has been made ionically conductive by the addition of at least one lithium salt, and Polymers that are made ionically conductive by adding a liquid electrolyte either in the polymer phase or in the mesoporous structure and preferably with a carrier phase for lithium ions, Even more preferably, N-Butyl-N-methyl-pyrrolidinium 4,5-dicyano-2-(trifluoromethyl)imidazole (Pyr 14 TDI) and an electrolyte containing a lithium salt of the LiTDI type; An electrolyte containing 1-methyl-3-propylimidazolium, 4,5-dicyano-2-(trifluoromethyl)imidazolide (PMIM-TDI), and lithium 4,5-dicyano-2-(trifluoromethyl)imidazolide (LiTDI) The electrolyte is impregnated with an electrolyte selected from the group formed by

[0130] The inorganic material E must be an electronic insulator. Oxides such as Al2O3, ZrO2, SiO2, or phosphates or borates can also be used. Nanoparticles of this material E form the mesoporous electrolyte separator layer.

[0131] 6. Impregnation with electrolyte to form a battery The assembly of the stack of layers intended to form the battery is followed by thermocompression and the resulting assembly must be impregnated with an electrolyte to form the battery. Said electrolyte must comprise a lithium ion carrier phase, as described in the previous section. The impregnation can be carried out at different steps of the method. Impregnation with liquid electrolyte in particular can be carried out especially on stacked and thermocompressed cells, i.e. after the battery is completed. Impregnation with liquid electrolyte in particular can also be carried out starting from the cut ends after encapsulation.

[0132] The carrier phase of the lithium ions can be an organic liquid containing a lithium salt. The carrier phase of the lithium ions can also be an ionic liquid (or a mixture of several ionic liquids) containing a lithium salt, or a mixture dissolved in an ionic liquid, optionally diluted with an organic solvent or a mixture of organic solvents containing a lithium salt that can be different from this. The carrier phase of the lithium ions can include a mixture of several ionic liquids. Ionic liquids that are liquid at ambient temperature (RTIL = room temperature ionic liquid) can be used.

[0133] In general, the cation of this ionic liquid is preferably selected from the group formed by the following cationic compounds and families of cationic compounds: imidazolium (such as the cation 1-pentyl-3-methylimidazolium, abbreviated PMIM), ammonium, pyrrolidinium, and / or the anion of this ionic liquid is preferably selected from the group formed by the following anionic compounds and families of anionic compounds: bis(trifluoromethanesulfonyl)imide, bis(trifluorosulfonyl)imide, trifluoromethylsulfonate, tetrafluoroborate, hexafluorophosphate, 4,5-dicyano-2-(trifluoromethyl)imidazolium (abbreviated TDI), bis(oxalato)borate (abbreviated BOB), oxalyldifluoroborate (abbreviated DFOB), bis(mandelato)borate (abbreviated BMB), bis(perfluoropinacolato)borate (abbreviated BFPPB).

[0134] The composition of the impregnated electrolyte and its lithium salt concentration can be adjusted according to the requirements of the intended use of the battery in terms of temperature, power, etc.

[0135] Thus, illustratively, for batteries designed to operate at high temperatures, Pyridine with lithium salts such as LiFSI and / or LiTFSI and / or LiTDI may be used. 14 FSI or Pyr 14TFSI type RTIL based electrolytes are preferred. Solvents resistant to high temperatures, such as GBL, may be added at levels less than 50%.

[0136] Additives may also be added to these formulations to reduce parasitic reactions on the surface of the electrode and / or on the surface of the current collector.

[0137] Advantageously, the carrier phase for the lithium ions is at least one ionic liquid, preferably PYR, optionally diluted with at least one solvent, such as γ-butyrolactone. 14 It includes at least one ionic liquid at ambient temperature, such as TFSI.

[0138] The lithium ion carrier phase may contain, for example, LiPF6 or LiBF4 dissolved in an aprotic solvent, or an ionic liquid containing a lithium salt. It is also possible to use ionic liquids, optionally dissolved in a suitable solvent and / or mixed with an organic electrolyte. For example, LiPF6 dissolved in EC / DMC can be used with LiTFSI:PYR 14 It can be mixed with ionic liquids containing lithium salts of the TFSI type (molar ratio 1:9) up to 50% by weight. For example, the mixture LiTFSI:PYR 13 FSI:PYR 14 It is also possible to create mixtures of ionic liquids that operate at lower temperatures, such as TFSI (molar ratio 2:9:9).

[0139] EC is the common abbreviation for ethylene carbonate (CAS number: 96-49-1). DMC is the common abbreviation for dimethyl carbonate (CAS number: 616-38-6). LITFSI is the common abbreviation for lithium bis-trifluoromethanesulfonimide (CAS number: 90076-65-6). PYR 13FSI is the common abbreviation for N-Propyl-N-Methylpyrrolidinium bis(fluorosulfonyl) imide. 14 TFSI is the common abbreviation for 1-butyl-1-methylpyrrolidinium bis(trifluoro-methanesulfonyl)imide.

[0140] The carrier phase of the lithium ions can be an electrolyte solution containing an ionic liquid. The ionic liquid is formed by a cation linked with an anion, and the anion and the cation are selected so that the ionic liquid is in a liquid state in the operating temperature range of the battery. The ionic liquid has the advantage of having high thermal stability, low flammability, non-volatility, low toxicity, and good wettability of ceramics, which is a material that can be used as an electrode material. Surprisingly, the mass percentage of the ionic liquid contained in the carrier phase of the lithium ions can be more than 50%, preferably more than 60%, and even more preferably more than 70%, which is in contrast to the lithium ion batteries of the prior art, where the mass percentage of the ionic liquid in the electrolyte must be less than 50% by mass, so that the battery maintains high capacity and voltage during discharge and good cycle stability. As shown in the application of US Patent Application Publication No. 2010 / 209783, above 50% by mass, the capacity of the prior art battery is degraded. This may be explained by the presence of polymer binders in the electrolytes of prior art batteries, which are weakly wetted by the ionic liquid and thus induce poor ionic conduction in the lithium ion carrier phase, causing degradation of the battery capacity.

[0141] PYR 14 TFSI and LiTFSI may also be used, and these abbreviations are described below.

[0142] Advantageously, the ionic liquid is bis(trifluoromethanesulfonyl)imide (TFSI - ) anion and / or bis(fluorosulfonyl)imide (FSI - ) linked to 1-ethyl-3-methylimidazolium (EMI + or EMIM + ), and / or n-propyl-n-methylpyrrolidinium (PYR 13 + ), and / or n-butyl-n-methylpyrrolidinium (PYR 14 + In an advantageous embodiment, the liquid electrolyte may be of the type Pyr 14 It contains at least 50% by weight of an ionic liquid that is TFSI.

[0143] Other cations that can be used in these ionic liquids are PMIM + Other anions that may be used in these ionic liquids include BF4 - , PF6 - , B.O.B. - , D.F.O.B. - , B.M.B. - , BPFPB - To form the electrolyte, a lithium salt such as LiTFSI can be dissolved in an ionic liquid or a solvent such as γ-butyrolactone, which is used as a solvent. γ-butyrolactone prevents the crystallization of the ionic liquid and induces a wider operating temperature range of the ionic liquid, especially at low temperatures. Advantageously, when the porous cathode comprises a lithiated phosphate, the carrier phase of the lithium ions comprises a solid electrolyte such as LiBH4 or a mixture of LiBH4 and one or more compounds selected from LiCl, LiI and LiBr. LiBH4 is a good conductor of lithium and has a low melting point, which facilitates its impregnation into the porous electrode, especially by immersion. Due to its extremely reducing properties, LiBH4 is not widely used as an electrolyte. The use of a protective film on the surface of the porous lithium phosphate electrode prevents the reduction of the cathode material by LiBH4 and avoids its degradation.

[0144] As explained above, many ionic liquids, especially Pyr 14 TFSI-LiTFSI and EMIM-TFSI can be used. EMIM-TFSI is Pyr 14 The main difference between these two ionic liquids is the potential range of stability over which they can be used. EMIM-TFSI is stable from 1 V to 4.7 V, while Pyr 14 -TFSI is stable from 0V to 5.0V, and for this reason, Pyr 14 -TFSI is preferred despite its lower liquidity.

[0145] However, TFSI-type lithium salts tend to corrode the substrate. For this reason, among ionic liquids and related salts, LiTDI is preferred as an anionic group of ionic liquids and / or lithium salts instead of or in addition to LiTFSI when the cathode is operated above 4.3V. It is observed that the simple addition of LiTDI-type salts to LiTFSI-type salts already reduces the corrosive effect of ionic liquids compared to metal substrates. LiTFSI contains sulfur, which tends to corrode the substrate, especially during operation at high temperatures. LiTDI does not corrode the substrate. TFSI can be used with substrates coated with a protective layer or with substrates made of materials that are more resistant to the corrosive effect of TFSI, such substrates being Mo, W, Cr, Ti, Ta.

[0146] In general, it is advantageous for the lithium ion carrier phase to comprise between 10% and 40% by weight of solvent, preferably between 30% and 40% by weight of solvent, even more preferably between 30% and 40% by weight of γ-butyrolactone, glyme, or PC.

[0147] In an advantageous embodiment, the lithium ion carrier phase comprises more than 50% by weight of at least one ionic liquid and less than 50% solvent, thereby limiting the safety and risk of fire in the event of failure of a battery comprising such a lithium ion carrier phase.

[0148] Advantageously, the lithium ion carrier phase is a lithium salt or mixture of lithium salts selected from the group comprising LiTFSI, LiFSI, LiBOB, LiDFOB, LiBMB, LiBPFPB and LiTDI; the concentration of the lithium salt is preferably between 0.5 mol / L and 4 mol / L, the Applicant having found that the use of an electrolyte having a sufficiently high concentration of lithium salt is favorable for very fast charging performance. a solvent or solvent mixture with a mass content of less than 40%, preferably less than or equal to 20%; this solvent can be, for example, γ-butyrolactone, PC, glyme. - Optionally, additives such as VC to stabilize the interface and limit parasitic reactions Includes.

[0149] In another embodiment, the lithium ion carrier phase is - 30 to 40% by weight of a solvent, preferably 30 to 40% by weight of γ-butyrolactone, or PC or a glyme, and - more than 50% by weight of at least one ionic liquid, preferably more than 50% by weight of PYR 14 TFSI Includes.

[0150] As an example, the lithium ion carrier phase is PYR 14 The electrolyte solution may be TFSI, LiTFSI, and γ-butyrolactone, preferably about 90% by weight PYR 14 The electrolyte solution may include TFSI, 0.7M LiTFSI, 2% LiTDI, and 10% by weight γ-butyrolactone.

[0151] 7. Description of Advantageous Embodiments Several embodiments of the battery according to the present invention are described below.

[0152] Generally, within the context of the present invention, the electrodes may be mesoporous. They may be thick (typically between about 10 micrometers and 100 micrometers), more particularly their thickness may be greater than 10 μm. They may be prepared by depositing agglomerates of nanoparticles. These agglomerates may have a polydisperse size and / or two different sizes (bimodal particle size distribution). In the finished state, these electrodes do not contain any binders (they may contain binders during the deposition of the nanoparticle suspension or paste, but these binders will be eliminated during the calcination heat treatment). They are partially sintered, i.e. the primary nanoparticles after the thermomechanical consolidation process are welded together by the phenomenon of "necking" to form a continuous three-dimensional mesoporous network (known to the skilled person, see for example ''Particulate Composites'' by RM German, Springer International Publishing 2016, p.26 / 27).

[0153] The porous anode according to the invention advantageously has a mesoporosity of less than 50%, preferably between 20% and 45%, preferably between 25% and 40%, with a value of about 35% being suitable. Advantageously, a nanolayer of an electronic conductor (for example carbon) is deposited on the mesoporous surface.

[0154] According to the invention, these mesoporous electrodes are coated with a nanometer-thick layer (this thickness is typically between about 0.8 nm and 10 nm) extending over their entire surface, where the surface is not the geometric surface of the layer but its entire mesoporous surface, the coating being applied also inside the pores. Said coating may be a conductive carbon coating.

[0155] After being coated with a conductive layer, the electrode is impregnated with a lithium ion conducting phase, which can be liquid or solid. If it is solid, it can be organic or mineral.

[0156] The electrode is bonded and sintered onto a substrate that is resistant to high temperature heat treatment, and the substrate may be made of, for example, W, Mo, Cr, Ti, and all alloys that contain at least one of these elements. Stainless steel may be suitable. It should be noted that if a free-standing electrode plate is prepared, this limitation of the resistance of the substrate or current collector to oxidation at the electrode heat treatment temperature no longer exists, since the electrode is not yet in contact with its current collector during the heat treatment.

[0157] The anode may more particularly be a TiNb2O7 anode (abbreviated as "TNO"), although the following description also relates to other active materials for the anode.

[0158] More specifically, a TiNb2O7 anode having a mesoporous volume of about 35% may be used, sized for a capacity of about 230 mAh / g.

[0159] It is possible to make a lithium-ion battery using these electrodes, in particular using a TiNb2O7 anode with about 35% mesoporous volume as described above.Five embodiments are described to enable those skilled in the art to implement the invention, but they are not intended to limit the scope of the invention in any way.

[0160] In a first embodiment, an attempt was made to increase the energy of the battery by selecting a cathode that operates at a high voltage.

[0161] The cathode current collector is a sheet of Mo, W, Ta, Ti, Al, stainless steel, Cr, or any alloy containing at least one of these elements, typically with a thickness of 5 μm to 20 μm. The cathode is made of LiCoPO4 with a mesoporous volume of about 35%. The cathode is about 90 μm thick, and a nanolayer of an electronic conductor (in this case, carbon) is deposited on the mesoporous surface. The cathode is sized for a capacity of about 145 mAh / g.

[0162] The separator is a layer of Li3PO4 about 6 μm thick with a mesoporous volume of about 50%.

[0163] The anode current collector is a sheet of Mo, W, Ta, Ti, Cu, Cr, Ni, Al, stainless steel or any alloy containing at least one of these elements, the thickness of which is typically between 5 μm and 20 μm. In the second embodiment of the invention, where the anode is first deposited on an intermediate substrate (extruded), it is also possible to use, for example, an aluminum electrode. The TiNb2O7 anode with a mesoporous volume of about 35% had a thickness of about 50 μm.

[0164] In either case, and more particularly in the second embodiment of the invention (wherein the anode is made in the form of a plate), the surface of the collector designed to be in contact with the electrode may be coated with a conductive coating, which in the case of the second embodiment of the invention will also play a role in forming the bond.

[0165] The cell was impregnated with an RTIL type ionic liquid (room temperature ionic liquid) formed by a mixture of Pyr14TFSI (1-butyl-1-methylpyrrolidinium bis(trifluoromethylsulfonyl)imide; CAS number 223437-11-4) with 20% GBL and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide; CAS number 90076-65-6; concentration of 0.7 M).

[0166] The following mixture may also be used: LiTFSI 0.7M + Pyr 14 TFSI+10% GBL+2% LiTDI.

[0167] Such a battery has a capacity of about 200mAh / cm 3 and a volumetric capacity density of approximately 610 mWh / cm 3 It achieves a volumetric energy density of 10 ...

[0168] One of the drawbacks of this battery is the high cost of the cathode material, based on its high cobalt content.

[0169] In a second embodiment, the LiCoPO4 cathode material is replaced with another high voltage cathode material that does not contain cobalt, namely the spinel material LiMn 1.5 Ni 0.5 O4, which contains manganese and for this reason the resistance of this cell at high temperatures is slightly more limited than in the first embodiment.

[0170] LiMn 1.5 Ni 0.5 The O4 cathode had a thickness of about 90 μm and a mesoporous volume of about 35% with a carbon nanolayer deposition; this cathode was sized for a capacity of about 120 mAh / g.

[0171] The separator, anode, cathode, and anode current collector, as well as the ionic liquid used to impregnate the cell, were the same as in the first embodiment.

[0172] This battery has a capacity of 210mAh / cm 3 and a volumetric capacity density of 625 mWh / cm 3It achieves a volumetric energy density of 10 ...

[0173] In a third embodiment, a cathode operating at a low voltage was used.

[0174] The cathode is a Li2O3 nano-particle cathode with a thickness of about 90 μm and a mesoporous volume of about 35%, with the deposition of a carbon nanolayer. 1.2 Ni 0.13 Mn 0.54 Co 0.13 O2; the cathode is sized to a capacity of approximately 200 mAh / g.

[0175] The separator is a layer of Li3PO4 about 6 μm thick with a mesoporous volume of about 50%.

[0176] The anode current collector is a sheet of Cu, Ni, W, Ta, Al, Cr, stainless steel, Ti, or Mo, or any alloy containing at least one of these elements, typically with a thickness of 5 μm to 20 μm. The TiNb2O7 anode, with a mesoporous volume of about 35%, has a thickness of about 80 μm, and a carbon nanolayer was deposited on the mesoporous surface.

[0177] The cell was impregnated with an ionic liquid of RTIL type, consisting of a mixture of LiTDI and LiTFSI, and more precisely formed of Pyr14TFSI with 0.7 M LiTFSI and 2% LiTDI.

[0178] This battery has a capacity of 285mAh / cm 3 and a volumetric capacity density of 720 mWh / cm 3It achieves a volumetric energy density of 10 ...

[0179] Note that this battery can operate over an extended temperature range (up to about +85° C.) if the cathode surface capacity is lower than the anode surface capacity.

[0180] A fourth embodiment relates to a high capacity microbattery having a cathode that operates at a low voltage.

[0181] The cathode current collector is a sheet of Mo, W, Ta, Ti, Al, stainless steel, Cr or any alloy containing at least one of these elements, the thickness of which is typically between 5 μm and 20 μm. If the electrode is made as an electrode plate, it is possible to use a sheet of aluminum if, after sintering, the nanoparticles from which the cathode is made are already fully crystallized, or if the collector is attached to the electrode.

[0182] The cathode is a Li2O3 with a thickness of about 16 μm and a mesoporous volume of about 35%, with the deposition of a carbon nanolayer. 1.2 Ni 0.13 Mn 0.54 Co 0.13 Made from O2, the cathode is sized for a capacity of approximately 200 mAh / g.

[0183] The separator is a Li3PO4 layer about 6 μm thick with a mesoporous volume of about 50%.

[0184] The anode current collector is a sheet of Cu, Ni, Al, or Mo, typically with a thickness of 5 μm to 20 μm. The TiNb2O7 anode, with a mesoporous volume of about 35%, has a thickness of about 14 μm, and a carbon nanolayer was deposited on the mesoporous surface.

[0185] The cell was impregnated with an RTIL type ionic liquid that consisted of Pyr14TFSI with 0.7 M LiTFSI and 2% LiTDI.

[0186] This microbattery has a capacity of 215mAh / cm 3 and a volumetric capacity density of 535mWh / cm 3 It achieves a volumetric energy density of 10 ...

[0187] These battery cells and batteries have excellent performance even at low temperatures. They can operate at temperatures below the crystallization temperature of the liquid electrolyte. When impregnation is performed with a polymer, the conductive properties of the polymer are enhanced over a wide temperature range.

[0188] An advantageous battery according to the invention has a cathode current collector made of a material selected from the group formed by Mo, Ti, W, Ta, Cr, Al, alloys based on the elements mentioned above, stainless steel, which is also NMC, preferably NMC 433The cathode also has a pore volume of 30-40%, which may be made of Li3PO4, a conductive layer being deposited in the pores. The separator is preferably a mesoporous layer of Li3PO4 with a thickness between 6 μm and 8 μm. The anode is preferably a layer of TiNb2O7 doped with halides and / or cerium and / or germanium and / or lanthanum and / or copper, said layer being impregnated with a liquid electrolyte containing a lithium salt. The anode current collector is selected from the group formed by Mo, Cu, Ni, alloys based on the base elements mentioned above, stainless steel. It is also possible to use aluminum. Other separator materials may be used.

[0189] Batteries according to the invention can be made with a wide variety of power ratings. In particular, by the method according to the invention it is possible to produce lithium-ion batteries with a capacity of more than 1 mAh. These are of particular interest in the form of high-power batteries, especially for use in electric vehicles. At intermediate power ratings they can be used in a variety of mobile electronic devices, such as mobile phones, laptops, and portable reading devices. Batteries with a capacity of 1 mAh or less are referred to herein as "microbatteries". For example, the cell of the fourth embodiment described above was produced by multiplying the thickness of the electrodes by a factor of six. Thus, with an anode thickness in the range of 50 μm to 80 μm, we obtain a battery of more than 550 Wh / l that can operate in a very wide temperature range and be recharged in less than 15 minutes. This battery is particularly well suited to the needs of hybrid and electric vehicles with fast recharging. EXAMPLES

[0190] In order to enable a person skilled in the art to reproduce the invention, in addition to the very precise embodiments described in the previous "Description of the Preferred Embodiments" section, further examples are given here, which are not intended to limit the invention.

[0191] Example 1: Synthesis of TNO nanopowder that can be used to prepare an anode according to the present invention Ti 0.95 Ge 0.05 Formulations of Nb2O7 nanoparticle agglomerates were synthesized from the following alkoxides: (i) Ge(OC2H5)4, molar mass 252.88 g / mol, density 1.14 g / cm 3 ; (ii) Ti(OC2H5)4, molar mass 228.11 g / mol, density 1.09 g / cm 3 ; (iii) Nb(OC2H5)4, molar mass 318.21 g / mol, density 1.268 g / cm 3 .

[0192] In a first step, citric acid was dissolved in ethylene glycol by heating to 80° C. In parallel, a mixture of ethoxides was prepared in a glove box, taking into account the stoichiometry of the target components.

[0193] In the second step, the mixture of alkoxides was introduced into the citric acid / ethylene glycol solution under strong stirring at ambient temperature. The reaction mixture was stirred at 80° C. for 12 hours, which caused the solution to gel.

[0194] The gel is then extracted and placed in an alumina crucible. The crucible is placed in a heating chamber at 250 °C for 12 hours. This heating step will allow the removal of excess ethylene glycol and activate the esterification reaction. The product is then calcined at 600 °C for 1 hour to remove most of the organic material.

[0195] A second heat treatment is then carried out at 800° C. Agglomerates of nanoparticles are then obtained (with a base size of 40 nm) crystallized in the space group I2 / mJCPDS:39-1407. These are pure monoclinic crystals.

[0196] FIG. 1 shows the electrochemical characteristics of the anode prepared according to this example.

[0197] Example 2: Preparation of mesoporous anode plate according to the present invention A slip consisting of agglomerated TNO nanoparticles was prepared. These agglomerates were approximately 100 nm in size and consisted of primary particles with a diameter of 15 nm. These agglomerates of nanoparticles were integrated into a slip with the following composition (percent by mass): 20% TNO nanoparticle agglomerates, 36% 2-butanone and 24% ethanol acting as a solvent, 3% phosphoric ester acting as a dispersant, 8.5% dibutylphtalate acting as a plasticizer, and 8.5% methacrylate resin acting as a binder.

[0198] The slip was cast into strips, then cut into plates and dried. These plates were then annealed at 600°C for 1 hour in air to obtain mesoporous ceramic plates that served as electrodes. The plates were then impregnated with a glucose solution and annealed at 400°C under N2 to achieve a conductive carbon nanocoating over the entire mesoporous surface of the electrode.

[0199] These plates are very useful in the production of high power batteries.

Claims

1. A method for manufacturing a porous anode for a battery comprising an anode, a separator and a cathode, the anode comprising a porous layer having a porosity between 25% and 50% by volume, preferably about 35% by volume, the pores having an average diameter of less than 50 nm, the method comprising: (a) a substrate and a mean primary diameter D between 2 nm and 100 nm, preferably between 2 nm and 60 nm 50 and a colloidal suspension or paste composed of monodisperse primary nanoparticles in agglomerate form or dispersed therein of at least one active material of an anode A having It is understood that the colloidal suspension or the paste also comprises a liquid component, The active material of anode A is preferably selected from niobium oxide and mixed oxides of niobium with titanium, germanium, cerium, lanthanum, copper or tungsten. Nb 2 O 5-δ , Nb 18 W 16 O 93-δ , Nb 16 W 5 O 55-δ , where 0≦x<1 and 0≦δ≦2; TiNb 2 O 7-δ , Ti 1-x M 1 x Nb 2-y M 2 y O 7-δ , Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7 , in the formula, M 1 and M. 2 are each at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, and Sn, and M 1 and M. 2 may be the same or different, and 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and 0≦δ≦0.3; Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , in the formula, M 1 and M. 2 each represents at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, and Sn; M 1 and M. 2 are identical or different from each other, M 3 is at least one halogen; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; TiNb 2 O 7-z M 3 z , Li w TiNb 2 O 7-z M 3 z , in the formula, M 3 is at least one halogen, preferably at least one halogen selected from F, Cl, Br, I, or mixtures thereof, with 0≦w≦5 and 0<z≦0.3; Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Ti 1-x La x Nb 2-y M 1 y O 7-z , Li w Ti 1-x La x Nb 2-y M 1 y O 7-z , Ti 1-x C.E. x Nb 2-y M 1 y O 7-z , Li w Ti 1-x C.E. x Nb 2-y M 1 y O 7-z , in the formula, M 1 is at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z<1, preferably 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z<0.3; Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-zM 2 z , Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x C.E. x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x C.E. x Nb 2-y M 1 y O 7-z M 2 z , in the formula, M 1 and M. 2 is at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, and Sn; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; It is understood that the compound is selected from the group formed by (b) depositing a layer from said colloidal suspension or paste provided in step (a) on at least one side of said substrate by a method selected from the group consisting of electrophoresis, extrusion, a printing method, preferably inkjet printing or flexographic printing, a coating method, preferably formed by doctor blading, roll coating, curtain coating, dip coating or slot die passing, (c) drying the layer obtained in step (b) and consolidating it by pressing and / or heating to obtain a porous layer. A method comprising:

2. The method further comprises step (d): (d) depositing a coating of an electronically conductive material on and within the pores of said porous layer, preferably selected from carbon or an electronically conductive oxide material, said electronically conductive oxide material preferably comprising: - Tin oxide (SnO 2 ), zinc oxide (ZnO), indium oxide (In 2 O 3 ), gallium oxide (Ga 2 O 3 ), mixtures of two of these oxides, for example indium oxide (In 2 O 3 ) and tin oxide (SnO 2 ) or a mixture of three of these oxides, or a mixture of four of these oxides; doped oxides based on zinc oxide, preferably with gallium (Ga), and / or aluminium (Al), and / or boron (B), and / or beryllium (Be), and / or chromium (Cr), and / or cerium (Ce), and / or titanium (Ti), and / or indium (In), and / or cobalt (Co), and / or nickel (Ni), and / or copper (Cu), and / or manganese (Mn), and / or germanium (Ge) for the doping, doped oxides based on indium oxide, preferably with tin (Sn), and / or gallium (Ga), and / or chromium (Cr), and / or cerium (Ce), and / or titanium (Ti), and / or indium (In), and / or cobalt (Co), and / or nickel (Ni), and / or copper (Cu), and / or manganese (Mn), and / or germanium (Ge) for the doping, doped tin oxide, preferably with arsenic (As), and / or fluorine (F), and / or nitrogen (N), and / or niobium (Nb), and / or phosphorus (P), and / or antimony (Sb), and / or aluminium (Al), and / or titanium (Ti), and / or gallium (Ga), and / or chromium (Cr), and / or cerium (Ce), and / or indium (In), and / or cobalt (Co), and / or nickel (Ni), and / or copper (Cu), and / or manganese (Mn), and / or germanium (Ge) for the doping; A step selected from 2. The method of claim 1, further comprising:

3. 3. The method according to claim 2, characterized in that the deposition of the coating of electronically conductive material is carried out by atomic layer deposition (ALD) or by immersion in a liquid phase containing a precursor of the electronically conductive material and subsequent conversion of the precursor into the electronically conductive material.

4. 4. The method according to claim 3, characterized in that the precursor is a carbon-rich compound, such as a carbohydrate, and that the conversion to an electronically conductive material is by pyrolysis, preferably in an inert atmosphere, or that the precursor is selected from organic salts containing one or more metal elements capable of forming an electronically conductive oxide after a heat treatment, such as calcination, and that the conversion to an electronically conductive material is a heat treatment, such as calcination, preferably carried out in air or in an oxidizing atmosphere.

5. 5. The method according to claim 1 , characterized in that the organic salt is preferably selected from an alcoholate of at least one metal element capable of forming an electronically conductive oxide after a heat treatment, such as calcination, preferably carried out in air or in an oxidizing atmosphere, an oxalate of at least one metal element capable of forming an electronically conductive oxide after a heat treatment, such as calcination, preferably carried out in air or in an oxidizing atmosphere, and an acetate of at least one metal element capable of forming an electronically conductive oxide after a heat treatment, such as calcination, preferably carried out in air or in an oxidizing atmosphere, and / or that the metal element is selected from tin, zinc, indium, gallium or a mixture of two, three or four of these elements.

6. The primary nanoparticles are in the form of aggregates or agglomerates, the aggregates or agglomerates having a mean diameter D between 50 nm and 300 nm, preferably between 100 nm and 200 nm. 50 6. The method according to claim 1, further comprising:

7. The porous layer obtained from step (c) is 10 m 2 / g to 500m 2 7. The method according to claim 1, characterized in that the specific surface area is between 1.0 and 1.5 μm / g.

8. The method according to any one of claims 1 to 7, wherein the layer obtained in step (c) has a thickness between 1 μm and 150 μm.

9. 9. The method according to claim 1, wherein the substrate is an intermediate substrate and the layers are separated after drying in step (c) to form a porous anode plate.

10. 1. A porous anode for a lithium ion battery comprising a porous layer having a porosity between 25 vol. % and 50 vol. %, preferably between 28 vol. % and 43 vol. %, even more preferably between 30 vol. % and 40 vol. %, The porous layer is - pores with an average diameter of less than 50 nm, a porous network of material A, comprising a coating of an electronically conductive material on and within the pores forming said porous network; The present invention is characterized in that it comprises The material A is preferably selected from niobium oxide and mixed oxides of niobium with titanium, germanium, cerium, lanthanum, copper or tungsten, Nb 2 O 5-δ , Nb 18 W 16 O 93-δ , Nb 16 W 5 O 55-δ , where 0≦x<1 and 0≦δ≦2; TiNb 2 O 7-δ , Ti 1-x M 1 x Nb 2-y M 2 y O 7-δ , Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7-δ , in the formula, M 1 and M. 2 Each of M is at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, and Sn, and may be the same or different from each other. 1 and M. 2 , 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and 0≦δ≦0.3; Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , in the formula, M 1 and M. 2 each represents at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, and Sn; M 1 and M. 2 may be the same or different from each other, M 3 is at least one halogen; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; TiNb 2 O 7-z M 3 z , Li w TiNb 2 O 7-z M 3 z , in the formula, M 3 is at least one halogen, preferably at least one halogen selected from F, Cl, Br, I, or mixtures thereof, and 0<z≦0.3; Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Ti 1-x C.E. x Nb 2-y M 1 y O 7-z , Li w Ti 1-x C.E. x Nb 2-y M 1 y O 7-z , in the formula, M 1 is at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z<1, preferably 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z<0.3; Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x C.E. x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x C.E. x Nb 2-y M 1 y O 7-z M 2 z , in the formula, M 1 and M. 2 is at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, and Sn; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; and wherein the compound is selected from the group formed by The anode is obtainable by the method according to any one of claims 1 to 9, Porous anode.

11. The electronic conductive material is preferably selected from carbon, electronic conductive oxide materials, - Tin oxide (SnO 2 ), zinc oxide (ZnO), indium oxide (In 2 O 3 ), gallium oxide (Ga 2 O 3 ), mixtures of two of these oxides, for example indium oxide (In 2 O 3 ) and tin oxide (SnO 2 ) or a mixture of three of these oxides, or a mixture of four of these oxides; doped oxides based on zinc oxide, preferably with gallium (Ga), and / or aluminium (Al), and / or boron (B), and / or beryllium (Be), and / or chromium (Cr), and / or cerium (Ce), and / or titanium (Ti), and / or indium (In), and / or cobalt (Co), and / or nickel (Ni), and / or copper (Cu), and / or manganese (Mn), and / or germanium (Ge) for the doping, doped oxides based on indium oxide, preferably with tin (Sn), and / or gallium (Ga), and / or chromium (Cr), and / or cerium (Ce), and / or titanium (Ti), and / or indium (In), and / or cobalt (Co), and / or nickel (Ni), and / or copper (Cu), and / or manganese (Mn), and / or germanium (Ge) for the doping, doped tin oxide, preferably with arsenic (As), and / or fluorine (F), and / or nitrogen (N), and / or niobium (Nb), and / or phosphorus (P), and / or antimony (Sb), and / or aluminium (Al), and / or titanium (Ti), and / or gallium (Ga), and / or chromium (Cr), and / or cerium (Ce), and / or indium (In), and / or cobalt (Co), and / or nickel (Ni), and / or copper (Cu), and / or manganese (Mn), and / or germanium (Ge) for the doping; 11. The anode according to claim 10, characterized in that it is selected from:

12. A method for producing a battery, preferably a lithium-ion battery, using a method for producing a porous anode according to any one of claims 1 to 9 or using a porous anode according to claim 10.

13. A method for manufacturing a battery comprising at least one porous anode according to claim 10 or 11, at least one separator and at least one porous cathode, comprising the steps of: (a) a first substrate and a second substrate are provided; a first colloidal suspension or paste is provided comprising aggregates or agglomerates of monodisperse primary nanoparticles of at least one active material of the anode A, the aggregates or agglomerates having a mean primary diameter D 50 is between 2 and 100 nm, preferably between 2 and 60 nm, and the aggregates or agglomerates have a mean diameter D 50 having The material A is preferably selected from niobium oxide and mixed oxides of niobium with titanium, germanium, cerium, lanthanum, copper or tungsten, Nb 2 O 5-δ , Nb 18 W 16 O 93-δ , Nb 16 W 5 O 55-δ , where 0≦x<1 and 0≦δ≦2; TiNb 2 O 7-δ , Ti 1-x M 1 x Nb 2-y M 2 y O 7-δ , Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7-δ , in the formula, M 1 and M. 2 are each at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, and Sn, and M 1 and M. 2 may be the same or different, and 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and 0≦δ≦0.3; Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , Li w Ti 1-x M 1 x Nb 2-y M 2 y O 7-z M 3 z , in the formula, M 1 and M. 2each represents at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, and Sn; M 1 and M. 2 may be the same or different from each other, M 3 is at least one halogen; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; TiNb 2 O 7-z M 3 z , Li w TiNb 2 O 7-z M 3 z , in the formula, M 3 is at least one halogen, preferably at least one halogen selected from F, Cl, Br, I, or mixtures thereof, with 0≦w≦5 and 0<z≦0.3; Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x La x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x Cu x Nb 2-y M 1 y O 7-z M 2 z , Ti 1-x C.E. x Nb 2-y M 1 y O 7-z M 2 z , Li w Ti 1-x C.E. x Nb 2-y M 1 y O 7-z M 2 z , in the formula, M 1 and M. 2 is at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, and Sn; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z≦0.3; Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Li w Ti 1-x Ge x Nb 2-y M 1 y O 7-z , Ti 1-x C.E. x Nb 2-y M 1 y O 7-z , Li w Ti 1-x C.E. x Nb 2-y M 1 y O 7-z , in the formula, M 1 is at least one element selected from the group consisting of Nb, V, Ta, Fe, Co, Ti, Bi, Sb, As, P, Cr, Mo, W, B, Na, Mg, Ca, Ba, Pb, Al, Zr, Si, Sr, K, Cs, Ce, and Sn; 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z<1, preferably 0≦w≦5, and 0≦x≦1, and 0≦y≦2, and z<0.3; It is understood that the compound is selected from the group formed by Bearing in mind that the first and / or second substrate may be a substrate capable of acting as a current collector or an intermediate substrate, a second colloidal suspension is provided comprising aggregates or agglomerates of monodisperse primary nanoparticles of at least one active material of the cathode C, the aggregates or agglomerates having a mean primary diameter D 50 is between 2 and 100 nm, preferably between 2 and 60 nm, and the aggregates or agglomerates have a mean diameter D 50 having a third colloidal suspension is provided, comprising aggregates or agglomerates of nanoparticles of at least one inorganic material E, the aggregates or agglomerates having a mean primary diameter D 50 is between 2 nm and 100 nm, preferably between 2 nm and 60 nm, and the aggregates or agglomerates have a mean diameter D 50 having (b) depositing an anode layer from the first colloidal suspension provided in step (a) on at least one side of the first substrate and a cathode layer from the second colloidal suspension provided in step (a) on at least one side of the second substrate by a method preferably selected from the group comprising printing methods selected from electrophoresis, extrusion, preferably inkjet printing and flexographic printing, and coating methods preferably selected from roll coating, curtain coating, doctor blade coating, coating by extrusion through a slot die, dip coating; (c) drying the anode and cathode layers obtained in step (b), optionally after separating said layers from their intermediate substrate, and consolidating each layer by pressing and / or heating, to obtain a porous, preferably mesoporous, inorganic anode layer and a porous, preferably mesoporous, inorganic cathode layer, respectively; (d) optionally, a coating of an electronically conductive material is deposited on and within the pores of said porous anode and / or cathode layers to form said porous anode and porous cathode; (e) depositing a porous inorganic layer from the third colloidal suspension provided in step (a) on said porous anode and / or said porous cathode obtained in step (d) by a technique preferably selected from the group comprising electrophoresis, extrusion, printing methods selected from inkjet printing and flexographic printing, and roll coating, curtain coating, doctor blade coating, coating by extrusion through a slot die, dip coating, (f) the porous inorganic layer of the structure obtained in step (e) is dried, preferably under air flow, and subjected to a heat treatment at a temperature higher than 130° C., preferably between about 300° C. and about 600° C., bearing in mind that, if necessary, before carrying out the heat treatment, the layer separated from its intermediate substrate is pressed onto a metal sheet capable of acting as a current collector; (g) said porous anode obtained in step d) or e) is stacked successively opposite said porous cathode obtained in step d) or e), the stack obtained being understood to comprise at least one porous inorganic layer as obtained in step e) forming said separator, (h) subjecting the stack obtained in step (g) to a hot pressing treatment at a temperature between 120° C. and 600° C. to obtain a battery comprising at least one porous anode, at least one separator and at least one porous cathode. A method comprising:

14. 14. The method according to claim 13, characterized in that said inorganic material E is an electrical insulator.

15. The product obtained from step (h) is an electrolyte composed of at least one aprotic solvent and at least one lithium salt; an electrolyte composed of at least one ionic liquid and at least one lithium salt; a mixture of at least one aprotic solvent, at least one ionic liquid and at least one lithium salt; a polymer made ionically conductive by adding at least one lithium salt, and Polymers that have been made ionically conductive by adding a liquid electrolyte either in the polymer phase or in the mesoporous structure and preferably with a lithium ion carrier phase, Even more preferably, N-butyl-N-methyl-pyrrolidinium 4,5-dicyano-2-(trifluoromethyl) imidazole (Pyr 14 an electrolyte comprising TDI; An electrolyte containing 1-methyl-3-propylimidazolium 4,5-dicyano-2-(trifluoro-methyl)imidazolide (PMIM-TDI), and lithium 4,5-dicyano-2-(trifluoro-methyl)imidazolide (LiTDI) 15. The method according to claim 13 or 14, wherein the substrate is impregnated with an electrolyte selected from the group comprising:

16. The active material of cathode C is LiCoPO 4 , LiMn 1.5 Ni 0.5 O 4 , LiFe, where 0<x<1 x Co 1-x P.O. 4 , x + y + z = 10 1/x Co 1/y Mn 1/z O 2 , Li 1.2 Ni 0.13 Mn 0.54 Co 0.13 O 2 , X is selected from Al, Fe, Cr, Co, Rh, Nd, Sc, Y, Lu, La, Ce, Pr, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and 0<x<0.1; 1.5 Ni 0.5-x X x O 4 , LiNi 0.8 Co 0.15 A 0.05 O 2 , M=Fe, Co, Ni or a mixture of these different elements Li 2 MPO 4 LiMPO, where F, M=V, Fe, T, or a mixture of these different elements 4 LiMSO where F and M are Fe, Co, Ni, Mn, Zn, and Mg 4 F, LiCoO 216. The method according to any one of claims 1 to 9 or any one of claims 12 to 15, wherein the compound is selected from the group formed by

17. A lithium-ion battery obtainable by the method according to any one of claims 12 to 16.

18. The electrolyte is preferably Pyr 14 18. The battery of claim 17, containing at least 50% by weight of an ionic liquid that is TFSI.

19. its cathode current collector is made of a material selected from the group comprising Mo, Ti, W, Ta, Cr, Al, alloys based on the elements mentioned above, stainless steel; its cathode is made of NMC, preferably NMC433, having a porous volume of 30-40% and a conductive layer of carbon deposited in the pores; The separator is preferably Li with a thickness between 6 μm and 8 μm. 3 P.O. 4 is a mesoporous layer of its anode is TiNb, 0≦δ≦0.3, preferably doped with halides and / or germanium; 2 O 7-δ said layer being impregnated with a liquid electrolyte containing a lithium salt; its anode current collector is selected from the group formed by Mo, Cu, Ni, alloys based on the elements mentioned above, stainless steel; 19. Battery according to claim 17 or 18, when dependent on any one of claims 13 to 16.

20. 20. A battery according to any one of claims 17 to 19, characterized in that it has electrodes with a thickness of more than 10 μm.

21. 21. Battery according to any one of claims 17 to 20, characterized in that it comprises an anode according to claim 10 or 11 or obtainable by the method according to any one of claims 1 to 9, and that said anode has a mass capacity of more than 200 mAh / g, preferably more than 250 mAh / g.

22. Use of a battery according to any one of claims 17 to 20 at temperatures below -10°C and / or above 50°C.